Identifying the optimal harvest stage for forage and biogas production from sweet sorghum under semi-arid Mediterranean conditions - Recep Irfan Nazli; Burak Beyaz; Asiye Sena Cavdar; Hasan Beytullah Donmez; Muhammad Azhar Nadeem (Biomass and Bioenergy, 2027)

Decoding PARP roles in breast cancer therapy resistance - Mohammad Abohassan; Farag M. Altalbawy; Majid S. Jabir; Thikra F. Hasan; Ashishkumar Kyada; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Munthar Kadhim Abosaoda; Muhammad Shahid Iqbal (Molecular Biology Reports, 2026)

Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

A Systematic review on sago starch-based bioplastics: Modification techniques, properties, and sustainability potentials - Muhammad Iskandar Ishaq; Muhammad Abdillah Hasan Qonit; I Gusti Komang Dana Arsana; Saptowo Jumali Pardal; Muhammad Ace Suhendar; Abdul Azis; Idawanni; Syariful Mubarok; Muhammad Luthfan Haziman (Next Research, 2026)

Exploring the bioactivity of Ageratum conyzoides L: Antioxidant, antimicrobial, and cytotoxic properties of flower extracts - Md. Safkat Zaman Fahim; Shyama Prosad Moulick; Sauda Sultana Mimi; Subarna Sandhani Dey; Md. Omar Sha Rafi; Sadia Afrin Chhanda; Dabashes Adhikery; Muhammad Mahfuz Hasan; Shahin Aziz; Tanvir Muslim (Next Research, 2026)

Improving sustainable water usage in extensive shrimp aquaculture in Bangladesh - Kelly Thornber; Mohammad Mahfujul Haque; Muhammad Abdur Rouf; Tamanna Fardoshi; Neaz A. Hasan; Md Rony Golder; Abul Bashar; Partho Pratim Debnath; Muhammad Meezanur Rahman; David Kawahigashi; Vishnumurthy Mohan Chadag; Charles R. Tyler (Aquaculture, 2026)

Volumetric 2D-3D RQD modeling from seismic refraction tomography for landslide susceptibility assessment in complex geological terrain - Muhammad Hasan; Lijun Su (Engineering Geology, 2026)

Genomic and phenotypic insights into the probiotic and antimicrobial potential of Bacillus amyloliquefaciens BCSIR-AJ strain from garlic chutney - Mohammed Ayaz; Md Murshed Hasan Sarkar; Mohammad Monerul Islam; Muhammad Irfanul Islam; Farjana Akter Koly; Md. Rakibul Hasan; Md Saddam Hossain; Saiful Islam (Archives of Microbiology, 2026)

The carbon cost of forest fragmentation: Size matters - Md. Mahadi Hasan; Nadiyah M. Alabdallah; Muhammad Waseem; Hui Liu (Trends in Ecology & Evolution, 2026)

A time adaptive weighting framework for enhanced vegetation health index based drought monitoring - Muhammad Waseem; Ali Hasan Jaffry; Mudassar Iqbal; Muhammad Ajmal; Jiaqing Xiao; Tao Yang; Pengfei Shi; Awais Naeem Sarwar (Remote Sensing Applications: Society and Environment, 2026)

Interactive Effects of Rhizobium and Arbuscular Mycorrhizal Fungi Reduced Heavy Metal Uptake and Enhanced Antioxidants and Yield in Cicer arietinum L. Grown in Metal Contaminated Sewage Sludge-amended Soil - Mudassara Hasan; Mohd Irfan Naikoo; Fauzia Naushin; Saurabh Kumar; Fareed A. Khan; Luai Muhammad Alhems (Water, Air, & Soil Pollution, 2026)

Potential Application of Tamarind Seed Extract as Coagulant Aid in Alum-Based Removal of Polyamide Microplastics - Muhammad Adli Hanif; Naimah Ibrahim; Man Yung Ho; Masitah Hasan; Farrah Aini Dahalan; Nabilah Aminah Lutpi; Norzila Othman; Mohamed Hasnain Isa (International Journal of Environmental Research, 2026)

Ecological and human health risks from railway-associated contaminants: a case study of trace metal and PAH pollution along a commuter line in Chittagong, Bangladesh - Mahbub Alam; Md. Samrat Mohay Menul Islam; Muhammad Abu Bakar; Md. Ashraful Islam; Suman Das; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Hasan Mahmud Babu (Environmental Geochemistry and Health, 2026)

Characteristics and risks of microplastic contamination in marine trash fish from the northern Bay of Bengal: implications for human health and local aquaculture industry - Muhammad Arifur Rahman; Md. Rakibul Hasan; Khadijatul Kubra Riya; Mohammad Abdul Baten Bhuyain; Sanjida Afrin Semme; Norhayati Ngah; Takaomi Arai; M. Belal Hossain (ENGINEERING Environment, 2026)

Non-invasive geophysical prediction of deep rock mass UCS in complex geological settings - Muhammad Hasan; Lijun Su; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2026)

In silico identification of novel PTP1B inhibitors by the investigation of molecular mechanism, QSAR, and DFT studies - Humaira Zulfiqar; Samira Akter; Jarin Tasnim; Muhammad Younis; Md. Mehedi Hasan; Sidra Manzoor; Sarnop Sarker; Muhammad Waqas; Khan Rajib Hossain (In Silico Pharmacology, 2026)
Protein tyrosine phosphatase 1B (PTP1B) is a well-known and promising drug target involved in the negative regulation of insulin and leptin signaling, and new anti-diabetic molecules for the treatment of type 2 diabetes are directly in its hands. A series of PTP1B inhibitors was discovered and characterized using in silico techniques, including virtual screening, molecular docking, ADMET profiling, toxicity prediction, VEGA-QSAR analysis, molecular dynamics (MD) simulation, and density functional theory (DFT) calculations. A starting library of 1000 anti-diabetic compounds was screened, and PubChem CID 44560696 was identified as the most successful hit. The most potent inhibitor was then identified as CID 44560744 through chemical analogy-based refinement, with a binding free energy of − 9.13 kcal/mol and the ability to form several stabilizing hydrogen bonds and hydrophobic interactions with the key catalytic residues. DFT-optimized geometry and docking revealed that the lead compound shows high stability and strong PTP1B inhibition, showing superior binding affinity compared to ursolic acid, which exhibited a lower binding energy of − 6.34 kcal mol −1 . The MD simulations showed that the PTP1B-ligand complex was structurally stable and compacted during the 200 ns simulation, with desirable profiles for RMSD, RMSF, Rg, SASA, and hydrogen bonds. The DFT and FMO analyses indicated that the compound exhibits extreme chemical reactivity and electron-transfer capability, owing to its low HOMO-LUMO gap, high softness, and moderate electrophilicity. The results of ADMET and toxicity evaluations (SwissADME, ProTox-II, and VEGA-QSAR) pointed to satisfactory solubility, non-carcinogenicity, no mutagenicity, and high pharmacological safety. Overall, the synergy of the computational methods has made CID 44560744 a lead scaffold for the development and optimization of selective PTP1B inhibitors for T2DM therapy.

Unraveling Luteolin’s Modulatory Effects on α-Synuclein Aggregation: A Combined Biophysical, Computational, and C. elegans Approach - Syed Moasfar Ali; Md Nadir Hassan; Nida Zaidi; Muhammad Uzair Ashraf; Mahmood Akbar; Aamir Nazir; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2026)

Red seaweed extract as a phycological biostimulant enhances groundnut drought tolerance: Integrated agronomic, physiological, and UAV-based insights - Malihatun Nesa; Sudip Sen; Md. Farhadur Rahman; Md. Moshiul Islam; S. M. Rafiquzzaman; Md. Main Uddin Miah; Abdul Kaium Tuhin; Hasan Muhammad Abdullah (Journal of Applied Phycology, 2026)

Assessing reach and perceptions of hygiene behaviour change interventions for people with disabilities and older adults: Multi-country matched cross-sectional study - Kazy Farhat Tabassum; Dewan Muhammad Shoaib; Md. Assaduzzaman Rahat; Mehedi Hasan; Dani Barrington; Ben Tidwell; Lauren D'Mello-Guyett; Anjali Sharma; Sheillah Simiyu; Ismail Hosen; Jenala Chipungu; Fachruddin Mangunjaya; et al. (International Journal of Hygiene and Environmental Health, 2026)

Tailoring subcritical water extraction conditions to enhance antioxidant selectivity from kale (Brassica oleracea var. acephala) - Nurul Faezawaty Jamaludin; Rosnah Shamsudin; Muhammad Hazwan Hamzah; Mohd Zuhair Mohd Nor; Muhamad Yusuf Hasan; Jaturapatr Varith (Innovative Food Science & Emerging Technologies, 2026)

Integrated Biochar-Based Amendments Enhance Soil Quality and Early Maize Development in Calcareous Soil - Yasin Demir; Halit Tutar; Hasan Er; Azize Doğan Demir; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Effect of Melatonin on Alleviating Chilling Injury in Cold-Stored ‘Kensington Pride’ Mangoes: A Comparative Evaluation of Long vs Short Dip Time - Mekhala Dinushi Kananke Vithana; Hafiz Muhammad Shoaib Shah; Mahmood Ul Hasan; Zora Singh (Journal of Plant Growth Regulation, 2026)
Mangoes ( Mangifera indica L.) are notably susceptible to chilling injury (CI) when stored below 13 °C. This temperature threshold is too high for extended storage. Therefore, the influence of postharvest immersion in melatonin (MT) (50, 75, 100 µmol L − 1 ) for 120 min on CI in ‘Kensington Pride’ mangoes kept at 5 ± 1 °C for 21 or 28 d was investigated. The most effective MT concentration was 75 µmol L − 1 causing 36.3% reduction in CI incidence compared to control. To facilitate adoptability in commercial practice, the influence of 120 min vs. 5- and 3-min immersions in 75 µmol L − 1 MT was also tested. The highest efficacy in reducing CI was shown by mangoes immersed in 75 µmol L − 1 MT for 5 min with 52.2% and 38.6% lower CI incidence and CI index, respectively, than the control. This improved chilling tolerance in MT-treated mangoes was achieved through reduced hydrogen peroxide (H 2 O 2 ) radicals, malondialdehyde (MDA) production, relative electrolyte leakage (REL) and lipoxygenase (LOX) activity while higher ascorbic acid (AsA) and glutathione (GSH) levels, and activities of ascorbate peroxidase (APX), glutathione reductase (GR) and monodehydroascorbate reductase (MDHAR). Fruit colour, soluble solids content (SSC), and titratable acidity (TA) were maintained in 75 µmol L − 1 MT treated fruit. MT was effective in reducing CI in mangoes up to 21 d at 5 ± 1 °C. Overall, immersing ‘Kensington Pride’ mangoes in 75 µmol L − 1 MT for 5 min before cold storage (5 ± 1 °C) shows high adoption potential to mitigate CI.

Distribution, source, and risk analysis of PAHs and trace elements in roadside soils of Dhaka-Bhanga expressway: a case study - S. M. Fazle Rabbi; Lamyea Rahman; Md. Samrat Mohay Menul Islam; Md. Ashraful Islam; Shariful Islam; Md. Mashfiqur Rahman Niloy; Muhammad Abu Bakar; Md. Rakibul Hasan; Md. Kamruzzaman (Environmental Monitoring and Assessment, 2026)

Removal of arsenic from aqueous solution using a surface-functionalized magnetic biochar derived from Chlorella - Muhammad Irfan; Israr Masood ul Hasan; Muhammad Jafir; Chang Li; Jie Hu; Muhammad Moeen ud din; Khalid Hussain; Yixing Zhu; Liugen Zheng (Marine Pollution Bulletin, 2026)

Systematic evaluation of wastewater surveillance of infectious diseases in low- and middle-income countries during the COVID-19 pandemic - Md Pervez Kabir; Asma Safia Disha; Muhammad Mainuddin Patwary; Mahadi Hasan; Sharif Mutasim Billah; Juvair Hossan; Afrin Laila Parvin; Mehedi Hasan; Tyson E. Graber; Egide Kalisa; Robert Delatolla (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Dual Z-scheme core-shell PANI-CeO2-Fe2O3-NiO heterostructured nanocomposite for dyes remediation under sunlight and bacterial disinfection” [Environ. Res. 215 (2022) 114140] - Faisal Mukhtar; Tauseef Munawar; Muhammad Shahid Nadeem; Muhammad Naveed ur Rehman; Shoukat Alim Khan; Muammer Koc; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Research, 2026)

State disaggregation for Non-Intrusive Load Monitoring (NILM) with calibrated bagged Seq2Point 1D convolutional neural networks - Md Mahadi Hasan Imran; Muhamad Zalani Daud; Muhammad Mukhtar Qureshi; Shahrizan Jamaludin; Atta-ur-Rahman; Md Meherullah; Abdullah Alqahtani (Energy and Buildings, 2026)

Impaired Glymphatic Function and Post-stroke Cognitive Decline after Intracerebral Hemorrhage: A Serial Neuroimaging Study - Nina H. Nariman; Md Faruk Hossain; Khader M. Hasan; Vahed Maroufy; Seth B. Boren; Spencer Solberg; Robert Suchting; Clark Sitton; Sean I. Savitz; Muhammad E. Haque (Translational Stroke Research, 2026)

Potential of 6-benzylaminopurine to Mitigate Salt Toxicity and Enhance Growth Performance in Tuberose (Polianthes tuberosa L.) - Muhammad Adnan Sadique; Safina Naz; Hasan Sardar (Journal of Plant Growth Regulation, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Evaluating the glycemic index of white and black rice varieties in Bangladesh: An exploratory comparative study - Md. Hanjala Pipil; Md Hasan Al Amin; Muhammad Javidul Haque Bhuiyan (Food and Humanity, 2026)

Urban vegetation loss: assessing built-up expansion and its implications on vegetation cover’s health and land surface temperature in the Accra Metropolitan Area, Ghana - Michael Batame; Emmanuel Yeboah; Elisha Njomaba; Isaac Sarfo; Selasi Klutsey; Oznur Isinkaralar; Muhammad Waseem; Ali Hasan Jaffry; Kaan Isinkaralar; Henry Adjanor Tetteh; Paul Kyeku; Ishmeal Quist; et al. (Theoretical and Applied Climatology, 2026)

Anxiolytic-like effects of p-coumaric acid via GABAergic interaction pathways: an in vivo and in silico study - Madhu Sah; Balaram Das; Ramesh Kumar Mandal; Raihan Chowdhury; Mohammad Y. Alshahrani; Muhammad Ali Khan; Anik Kumar Saha; U Ching Aoung Chak; Sadia Akhter; Md. Fazla Alahi Nikson; Shama Mohanta; H. M. Shadid Hossain Snigdha; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comment on “Prescribing patterns of glucagon like peptide-1 receptor agonists in the Swedish capital region: a register-based cross-sectional study” - Muhammad Salman; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

EEG-based cognitive state classification using a leakage-safe stacked ensemble learning approach - Md Rafiqul Islam; Riad Hasan; Md Abu Layek; Muhammad Aminur Rahaman (Next Research, 2026)

Three Characterized Probiotics from Dairy Sources—Weissella confusa (ProY 5.1), Enterococcus lactis (ProY 5.3), and Leuconostoc lactis (RM 2.1)—Exhibit Potential for Antidiarrheal Effects - Jannatul Ferdous; Md. Saddam Hossain; Palash Kumar Sarker; Md. Shimul Bhuia; Md. Sakib Al Hasan; Raihan Chowdhury; Md. Sarafat Ali; Md. Robiul Auwal; Keshob Chandra Das; Muhammad Torequl Islam; Abu Hashem; Md. Salimullah (Probiotics and Antimicrobial Proteins, 2026)

Fecal microbiota transplantation in inflammatory bowel disease: a systematic review and meta-analysis of randomized controlled trials (2020–2025) - Sania Ikram; Muneeb Ullah; Juho Lee; Nurhasni Hasan; Jin-Wook Yoo; Raees Khan; Muhammad Naeem (Inflammopharmacology, 2026)

Development and evaluation of climate-smart aquaculture interventions to enhance livelihood resilience in salt farming communities of Bangladesh - Md. Rakibul Hasan; Muhammad Meezanur Rahman; Seikh Razibul Islam; Md Anisuzzaman; Khadijatul Kubra Riya; Takaomi Arai; Norhayati Ngah; M. Belal Hossain (Aquaculture International, 2026)

Soil amendments enhance phenolic defense in canola, suppressing cabbage aphid population and improving yield performance - Muhammad Wajid Javed; Mansoor–ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2026)

Development of a new shoe sizing system for adult males to overcome fitting inconsistencies between foot and shoe size - Md. Imrul Kayes Limon; Md. Mofazzal Hossin; Md. Sydur Rahman; Muhammad Naimul Hasan; Azizur Rahman; Md. Elias Uddin; Md. Samsul Arefin (Next Research, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Combining anxiolytic activity of thymol and trans-ferulic acid: a potential GABAergic intervention - Md. Hanif Munshi; Noshin Tasnim Yana; Imam Hossen Rakib; Emon Mia; Nusrat Jahan Tohfa; Md. Sakib Al Hasan; Md Abu Sayeed; Mst. Sumaia Akter; Md. Arif Hossain; Muhammad Torequl Islam; Md. Shimul Bhuia; Mushtaq Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Continuous-Flow Electrocoagulation for Hexavalent Chromium Reduction in Nickel Mining Wastewater: Insights into Optimization and Mechanisms - Muhammad Risal Rusman; Muhammad Sonny Abfertiawan; Faiz Hasan; Mindriany Syafila; Marisa Handajani (Mine Water and the Environment, 2026)
Indonesia’s extensive laterite nickel reserves drive substantial nickel mining activities yet pose environmental risks due to the wastewater’s hexavalent chromium (Cr(VI)) contamination. This study evaluates a continuous-flow electrocoagulation reactor, using aluminum and iron electrodes to remove Cr(VI) from nickel mining wastewater. Optimization via a Box-Behnken design examined current intensity, flow rate, and reactor flow distance. Results revealed that iron electrodes achieved superior Cr(VI) removal efficiency of up to 99% at a flow rate of 0.99 L/min, current intensity of 2 A, and reactor flow distance of 165,6 cm, whereas aluminum electrodes attained a maximum removal efficiency of 83% under optimal conditions of 2.9 A, 0.93 L/min, and 338 cm. Iron electrodes also demonstrated lower specific electrical energy consumption (0.48 kWh/g Cr(VI)) than aluminum (1.39 kWh/g Cr(VI)). Kinetic studies indicated that Cr(VI) removal on aluminum electrodes aligns with a pseudo-first-order model, while iron electrodes follow a second-order model, highlighting a shift from physical to chemical adsorption mechanisms. Adsorption isotherms further supported these findings, with Freundlich isotherms fitting the aluminum electrodes (R 2 = 0.998), suggesting heterogeneous, multilayer adsorption, and Langmuir isotherms fitting the iron electrodes (R 2 = 0.988), indicating homogeneous, monolayer adsorption. This study underscores electrocoagulation’s potential as an energy-efficient and sustainable solution for Cr(VI) removal in mining wastewater treatment.

Piperine exerts anti-inflammatory effects and antagonises the properties of celecoxib and ketoprofen: in vivo and molecular docking studies - Rubel Hasan; Md. Shimul Bhuia; Raihan Chowdhury; Muhammad Ali Khan; Modhurima Mazumder; Noshin Tasnim Yana; Marcus Vinícius Oliveira Barros de Alencar; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (Natural Product Research, 2026)

Betaine-loaded Foeniculum vulgare@Fe-MOF: A novel approach to combat bleomycin-induced hepatotoxicity in rats - Sana Batool; Iftikhar Ahmed; Calvyn Howells; Li Haitao; Muhammad Saqib Saif; Tuba Tariq; Riaz Hussain; Muhammad Mahmood Ahmad; Sobia Tauheed; Chaokun Hong; Tauseef Munawar; Shahbaz Gul Hassan; et al. (Journal of Environmental Chemical Engineering, 2026)

Built-in electric field-governed ion sieving in interlayer-engineered TiN–MXene heterostructure anodes for dominant aqueous zinc-ion storage - Inaam Ullah; Ayesha Irfan; Mai Li; Chenxi Li; Samira Saddique; Salamat Ali; Waqar ul Hasan; Muhammad Irfan; Caiyuan Xiong; Jinbo Ming; Qinglin Deng; Chunrui Wang; et al. (Chemical Engineering Journal, 2026)

In-situ sequential topotactic transformation of ZIF-8 to N-doped Zn-oxide/sulfide with defect engineering for efficient radiocesium capture - Muhammad Ikram; Toshio Yamaguchi; Iltaf Muhammad; Qirui Wang; Hongyan Liu; Shahzad Afzal; Israr Masood ul Hasan; Yongquan Zhou (Chemical Engineering Journal, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

Assessment of antiemetic potential of schaftoside through modulation of dopaminergic, serotonergic and muscarinic signaling pathways: in vivo and in silico investigations - Md. Shakil Ahmmed; Rakib Hossan; Tawfik Rakaiyat Ripu; Towfiqur Rahman; Mohammad Y. Alshahrani; Emon Mia; Proma Mandal; Md. Sakib Al Hasan; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Designing 3D-printed concrete with ternary blended mortars incorporating fly ash and silica fume: effects of low water-binder ratios on workability and strength - Kamrul Hasan; Aizat Alias; Mehedi Hasan; Fadzil Mat Yahaya; Khairul Fikri Muhammad (Innovative Infrastructure Solutions, 2026)
3D-printed concrete (3DPC) construction has gained global attention as an innovative and promising technique. However, the high cement content in 3DPC raises sustainability concerns, presenting a challenge for implementing sustainable processes. To address the issue, this research uses a low water-to-binder (w/b) ratio and incorporates silica fume (SF) and fly ash (FA) as partial cement replacements to reduce cement consumption and enhance sustainability. Three w/b ratios (0.33, 0.35, 0.37) and varying superplasticizer (SP) doses (0%, 0.25%, 0.5%, 0.75%, 1%) were tested, with 10% SF and 20% FA. The study investigated the physical, chemical, and morphological properties of the mix, alongside fresh, hardened, and durability properties, including workability, dry bulk density, compressive strength, dynamic modulus of elasticity, water absorption, and sulfate resistance. The results showed that a higher w/b ratio increased workability, with the w/b 0.37 mix exhibiting 50.71% higher workability than the w/b 0.33 and 45.09% higher than the w/b 0.35 for SP0 at 0 min. Besides, both a lower w/b ratio and increased SP content improved dry bulk density, compressive strength, and dynamic modulus of elasticity, with performance peaking at a 0.5% SP dosage in mix SP2. Additionally, reducing the w/b ratio decreased water absorption from 5.54% at 0.37 to 4.22% at 0.33 and lowered mass loss across all mixes; notably, the 0.33 mix with SP2 achieved the lowest mass loss (0.89%) and strength loss (3.12%). Despite these improvements, the use of SP increased production costs by 14.32%, while $$ CO_{2}$$ emissions rose only slightly by 0.89%.

Biostimulant effect of seaweed extracts on micropropagation of important ground macrophyte Micranthemum tweediei and data-driven insights using machine learning and response surface regression - Esra Özcan; Seyid Amjad Ali; Muhammad Asim; Hasan Hüseyin Atar (Aquaculture International, 2026)
Commercially viable in vitro cultivation of ornamental and aquatic plants depends heavily on the proper use of bio-stimulants that encourage healthy and uniform growth. This study explores the role of two seaweed extracts, Jania rubens and Cystoseira barbata , in promoting in vitro micropropagation of Micranthemum tweediei (Monte Carlo), a widely used aquatic plant. Culture medium was enriched with different concentrations (2.5–20.0%) of J. rubens and C. barbata extracts with 1–4 g L −1 Murashige and Skoog (MS) nutrient media. Considering all results, J. rubens extract was more effective than C. barbata in terms of micropropagation and chlorophyll content of M. tweediei . Addition of 5% J. rubens extract to 2 g L −1 MS medium (approx. half strength) resulted in a 47% increase in clump diameter (5.18 cm), a 173% increase in rooting rate (92.4%), and a 108% increase in shoot clump fresh weight (3.6 g), and 84%, 115%, and 87% increases in chlorophyll a , b , and total chlorophyll levels, respectively, compared to the control 2 g L −1 MS medium without extract. Micropropagation parameters resulting from 4 g L −1 MS (approx. full strength) supplemented with J. rubens extract were lower than those obtained from 2 g L −1 MS. Unlike J. rubens , C. barbata showed the highest micropropagation when 10% extract was added to 4 g L −1 MS nutrient medium, resulting in a clump diameter of 5.11 cm, 42.8% rooting, a fresh clump weight of 7.37 g, and a dry clump weight of 0.59 g. Propagated in vitro plants were easily acclimated to external conditions in aquariums. Results of response surface regression analysis (RSRA) confirmed the results, and MS concentration influenced the plant biomass and chlorophyll contents, whereas seaweed type and concentration regulated the clump diameter and rooting. Application of machine learning models validated and predicted the outcomes precisely. Multi-layer perceptron (MLP) model exhibited superior predictive accuracy for morphological traits, while more predictive accuracy of chlorophyll parameters was attributed to Random Forest (RF) model. This study has shown for the first time that aquatic plants can be micropropagated more successfully and at lower cost by adding seaweed extracts to in vitro nutrient media without the need for growth regulators.

Enhancing resilience and sustainability: an inductive approach to innovations in cruise industry - Muhammad Hasan Ashraf; Naima Saeed; Kevin Cullinane; Martin Dresner (Transportation Research Part D: Transport and Environment, 2026)

Nanobubble-enabled wetting control in membrane distillation via interfacial modulation - Mingyi Jia; Jianhao Qian; Muhammad Usman Farid; Jehad A. Kharraz; Shadi W. Hasan; Samir Kumar Khanal; Alicia Kyoungjin An (Chemical Engineering Journal, 2026)

Succinic acid enhances sedative activity of diazepam through GABAergic receptor modulation: Evidence from behavioral approach and computational insights - Md. Sakib Al Hasan; Yasin Emon; Mohammad Y. Alshahrani; Imam Hossen Rakib; Emon Mia; Abida Sultana; Akayed Hasan; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Water footprint assessment under deficit irrigation: a comparative analysis of field data and CROPWAT model agreement in semi-arid regions - Hasan Er; Halit Tutar; Ilker Angin; Abdullah Muratoglu; Mehdi Rahimi; Muhammad Farooq (Irrigation Science, 2026)

Unlocking geothermal potential in abandoned hydrocarbon and exploration wells: a sustainable energy solution - Muhammad Affan Uddin Ali Khan; Syed Imran Ali; Shaine Muhammadali Lalji; Aliza Hussain; Wajih Hasan; Munira Akhtar Khan; Syed Danish Rasool (Arabian Journal of Geosciences, 2026)

Seasonal variation, spatial distribution, and health risk assessment of trace elements in a major canal of Chittagong, Bangladesh: Implications for irrigation suitability - Riyadh Hossen Bhuiyan; Md. Shazzadur Rahman; Muhammad Edris Ali; Md. Golam Mostafa; Md. Mazadur Rahaman Bhuiyan; Md. Zahid Hasan Bhuyan; Md. Ripaj Uddin (Regional Studies in Marine Science, 2025)

Metal organic frameworks derived novel metal sulfide (KCoZnS) nanosheet as an efficient collector for cesium ions - Muhammad Ikram; Hongyan Liu; Iltaf Muhammad; Qirui Wang; Shahzad Afzal; Masood Ul Hasan Israr; Asad Ali; Yongquan Zhou (Journal of Environmental Chemical Engineering, 2025)

Next-generation wearable ECG systems: Soft materials, AI integration, and personalized healthcare applications - Bangul Khan; Rana Talha Khalid; Muhammad Hasan Masrur; Muhammad Awais; Bilawal Khan; Bee Luan Khoo (Chemical Engineering Journal, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Beyond traditional diagnosis: aptamer-based microRNA detection for the early diagnosis of periodontitis - Muhammad Usman Ashraf; Khairul Mohd Fadzli Mustaffa; Nurul Wahida Mohd Hasan; Maaz Anwer Memon; Danial Qasim Butt; Rizwan Mahmood; Wan Nazatul Shima Shahidan (Molecular Biology Reports, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Molecular detection and prevalence of colistin-resistant Escherichia coli in poultry and humans: a one health perspective - Muhammad Najam Ul Huda; Muhammad Zubair Shabbir; Adnan Hasan Tahir; Awais Ali Ahmad; Umar Bin Zahoor; Waqas Ahmad; Ali Raza; Farhan Afzal; Abdur Rauf Khalid; Muhammad Abu Bakr Shabbir (Brazilian Journal of Microbiology, 2025)

Biocontrol and beyond: the versatile roles of Streptomyces in agriculture - Tajrin Jahan; Muhammad Fazle Rabbee; Md. Mobinul Islam; Md. Ahsan Habib; Md. Sohel Rana; Avijicth Basak; Randa Mohammed Zaki; Md. Mohidul Hasan; Kwang-Hyun Baek (Reviews in Environmental Science and Bio/Technology, 2025)

Utilization of the desalination brine for enhancing inland shrimp farming in Kuwait - Sherain N. Al-Subiai; In Kwon Jang; Sumaiah Hussain; Enas Al-Hasan; Muhammad Al-Foudari; Ali Al-Odwani; Sarah Al-Jutaili; Tae-Jin Choi (Desalination, 2025)

Application of geophysical methods for 2D and 3D geomechanical modeling in geotechnical engineering - Muhammad Hasan; Lijun Su (Computers and Geotechnics, 2025)

Role of Microbial Secondary Metabolites in Enhancing Pesticide Biodegradation: A Critical Review on Solubility, Mobility, and Environmental Risk of Metabolites - Alvina Setiawardani; Rury Eryna Putri; Wisnu Hasan; Sonny Kristianto; Wimbuh Tri Widodo; Muhammad Tjammal Rehman; Mohamad Hamdi Zainal-Abidin (Water, Air, & Soil Pollution, 2025)

Oleuropein modulates anti-inflammatory activity of celecoxib and ketoprofen through cyclooxygenase pathway: in vivo, in silico and pharmacokinetics approaches - Nishat Jahan; Manoj Mandal; Imam Hossen Rakib; Md. Sakib Al Hasan; Emon Mia; Noshin Tasnim Yana; Mohammed Alfaifi; Faisal H. Altemani; Rakib Hossan; Umme Habiba Sumaya; Ali Mohamod Wasaf Hasan; Md. Abu Sayeed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synergistic Sedative Activity of Indirubin on Diazepam in Thiopental Sodium-induced Sleeping Mice: A Potential GABAergic Transmission - Tamanna Khatun; Abdul Malik; Abdullah K. Alshememry; Rubel Hasan; Md.Shimul Bhuia; Raihan Chowdhury; Sabiha Fatima; Dipu Bishwas; Sonaly Akter Mukty; Ishrat Jahan Disha; Mehedi Hasan Bappi; Muhammad Torequl Islam (Molecular Neurobiology, 2025)

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

Deciphering near-surface architecture and landslide triggers in granitic environments: A regression-driven multiphysics modeling framework for geoengineering integrity - Adedibu Sunny Akingboye; Andy Anderson Bery; Hui Tang; Meng Heng Loke; Muslim Babatunde Aminu; Taiwo Adewumi; Muhammad Hasan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Metal organic frameworks (MOFs) synthesis and their use as a loading agent in oxidative stress-based diseases - Muhammad Saqib Saif; Sana Batool; Yusra Majeed; Asadullah; Tuba Tariq; Li Haitao; Yanjun Duan; Ghazala Mustafa; Murtaza Hasan (Journal of Environmental Chemical Engineering, 2025)

Engineering of Foeniculum vulgare with material science: La2O3-CeO2-CuO nanocomposites to revolutionize photocatalysis and antimicrobial challenges - Sana Batool; Iftikhar Ahmed; Calvyn Howells; Muhammad Saqib Saif; Tuba Tariq; Muhammad Waqas; Li Haitao; Yanjun Duan; Mumtaz Hussain; Mansour Ghorbanpour; Ghazala Mustafa; Murtaza Hasan (Journal of Environmental Chemical Engineering, 2025)

Mapping seismic risk in Rangpur Division, Bangladesh: an integrated geospatial approach - Mehedi Hasan; Muhammad Al-Amin Hoque; Biswajeet Pradhan (Spatial Information Research, 2025)
Rangpur Division in Bangladesh lies near the active Dauki Fault, yet few studies have fully assessed its earthquake risk. Most research focuses separately on hazard or vulnerability, often ignoring mitigation and detailed spatial analysis. This study fills that gap by using a geospatial multi-criteria approach that integrates hazard, vulnerability, and mitigation indicators into one risk assessment model. Employing Geographic Information Systems (GIS), Analytic Hierarchy Process (AHP), and Multi-Criteria Decision Analysis (MCDA) in Python, nine hazard criteria, seven vulnerability indicators, and five mitigation factors were modeled as weighted raster layers. These layers were combined to produce high-resolution maps and a seismic risk map with five risk levels from very high to very low. Model validation showed strong predictive ability (AUC = 0.857) and consistency (CR < 0.1). Results reveal that 21.43% of Rangpur is at very high risk, mainly due to proximity to fault lines and dense population, while only 10.62% shows strong mitigation capacity. This highlights the urgent need for better disaster preparedness, infrastructure improvement, and public awareness. The spatial outputs provide valuable guidance for policymakers on urban planning, risk reduction, and resilience-building in the region.

Climate Change Impacts on Fruit Crops and Mechanisms of Stress-Induced Disease Dynamics for Resilience Strategies - Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Current status, challenges, and opportunities of agroforestry in rice-based mixed farming systems in Northern Bangladesh - Muhammad Ziaul Hoque; Minhaz Ahmed; Sharif Ahmed; Md. Zahid Hasan; Md. Ataur Rahman; Humnath Bhandari (Agroforestry Systems, 2025)

Antiemetic Efficacy of Nodakenin Through Muscarinic, Dopaminergic, and Serotonergic Receptor Modulation: Combined Experimental and Computational Approach - Towfiqur Rahman; Feroz Khan Nun; Tawfik Rakaiyat Ripu; Md. Sakib Al Hasan; Md. Shakil Ahmmed; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Imam Hossen Rakib; Emon Mia; Md. Shimul Bhuia; Muhammad Torequl Islam (Cell Biochemistry and Biophysics, 2025)

Enhanced ammonia nitrogen filtration using NaOH-activated Manihot utilissima peel carbon: Application in recirculating aquaculture systems for Nile tilapia - Said Ali Akbar; Muhammad Hasan; Zulkarnain Jalil; Ilham Zulfahmi; Muhammad Iqhrammullah; Nila Safina (Chemosphere, 2025)

Dispersion stability of a water-based ternary hybrid nanofluid with Al2O3, CuO, and graphite: an experimental and RSM modeling approach - Md. Ramim-Ul Hasan; Tanjimur Rashid; Md. Emdadul Hoque; Muhammad Aziz; Md. Sanowar Hossain (Next Research, 2025)

Cinnamon bark oil application and modified atmosphere packaging alleviates chilling injury, ethylene production and maintains antioxidant system in persimmons - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Muhammad Rizwan Azhar; Eben Afrifa-Yamoah; Andrew Woodward (Food Chemistry, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Mechanistic insights into microplastic-induced reproductive toxicity in aquatic organisms: A comprehensive review - A K M Munzurul Hasan; Md. Foysul Hossain; Minhaz Uddin; Muhammad Tariq Khan; Uddin Md Saif; Mohamed Hamed; Christopher J. Martyniuk; Douglas P. Chivers (Aquatic Toxicology, 2025)

Genome-wide Expression of Hsp60 in Anadromous Hilsa Shad (Tenualosa ilisha) during their Downstream Migration across Variable Habitat Temperatures - Md. Toasin Hossain Aunkor; Afroza Pervin; Md. Jubayer Ahmed; Md. Nazmul Hasan; Mohammad Mehedi Hasan Khan; Muhammad Anamul Kabir; Md. Faruque Miah (Thalassas: An International Journal of Marine Sciences, 2025)

Biochemical validation for the therapeutic use of Plumeria rubra in coagulation disorders: a study combining in silico, in vitro, and in vivo approaches - Imran Ahmad Khan; Muhammad Anwar; Sarmad Frogh Arshad; Athar Hussain; Muhammad Usman; Mohammed Nadeem Ansari; Hasan Junaid Arshad; Asma Shah Rukh; Qurat Ul Ain; Maliha Khalid Khan (Protoplasma, 2025)

Optimizing Irrigation Strategies for Sorghum × Sudangrass Hybrid on Ethanol Yield, Water Use Efficiency, and Drought Adaptation in Semi-Arid Regions - Halit Tutar; Hasan Er; Erdal Gönülal; Şenol Çelik; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Advancing comfort and efficiency: Radiant heating and cooling systems for sustainable architecture - Tarek Abedin; Md Mahfuzur Rahman; Zihad Hasan Joy; Khaled Alnamasi; Irfan Anjum Badruddin; Muhammad Nasir Bashir; Mohammad Nur-E-Alam (Building and Environment, 2025)

Caffeine and sclareol take the edge off the sedative effects of linalool, possibly through the GABAA interaction pathway: molecular insights through in vivo and in silico studies - Muhammad Torequl Islam; Md. Sakib Al Hasan; Jannatul Ferdous; Noshin Tasnim Yana; Emon Mia; Imam Hossen Rakib; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Md. Shimul Bhuia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Anti-arthritic potential of linalool: in vitro, in vivo, and in silico mechanistic insights for safer therapeutic applications - Shoyaeb Ahammed; Raihan Chowdhury; Md. Sakib Al Hasan; Emon Mia; Md. Showkoth Akbor; Md. Tahajul Islam; Rokibul Islam Chowdhury; Md. Sabbir Hossain; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Zainab M. Almarhoon; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Daidzin Enhances the Anticonvulsion Effects of Carbamazepine and Diazepam, Possibly Through Voltage-Gated Sodium Channels and GABAA-Dependent Pathways - Muhammad Torequl Islam; Md. Sakib Al Hasan; Jannatul Ferdous; Shoyaeb Ahammed; Md. Shimul Bhuia; Salehin Sheikh; Noshin Tasnim Yana; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Saifuzzaman (Molecular Neurobiology, 2025)

Comment on: “Genome-wide association study of direct oral anticoagulants and their relation to bleeding” - Muhammad Umar Farooque Khoso; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2025)

Precision in vitro propagation by integrating response surface methodology and machine learning for Glossostigma elatinoides (Benth) Hook. F - Esra Özcan; Seyid Amjad Ali; Muhammad Aasim; Hasan Hüseyin Atar (In Vitro Cellular & Developmental Biology - Plant, 2025)
Optimization of in vitro organogenesis of Glossostigma elatinoide s (Benth) Hook. f. was targeted in this study. The experiment was designed with the help of design of experiment (DOE) of response surface methodology (RSM) model. Murashige and Skoog (MS) basal salt, sucrose, and agar were used as input factors and a total of 15 runs were used for optimization. Results were analyzed by ANOVA and response surface regression analysis (RSRA) followed by prediction and validation via different machine learning (ML) models. Results of ANOVA revealed the impact of different combinations on output parameters. Results of RSRA illustrated the relationship between input and output parameters. Pareto chart analysis showed the significant impact of MS on clump diameter, fresh wt., and dry wt. Normal plot analysis illustrated the positive impact of MS on all output parameters and increased proportionally with MS concentration. Results of heatmap and network analysis also demonstrated the significance of MS on all output parameters. Comparison of ML models depicted the better performance of multilayer perceptron (MLP) model for rooting ( R 2 = 0.957), fresh wt ( R 2 = 0.806), and dry wt ( R 2 = 0.812). Conversely, the support vector regression (SVR) model demonstrated superior prediction for clump diameter ( R 2 = 0.809). Among the tested models, the SVR model showed the weakest performance, aside from clump diameter, while LightGBM achieved scores close to those of the RF and MLP models across all metrics. The findings clearly indicate that the adopted protocol is well-suited for the effective commercial propagation of the aquatic G. elatinoides plant.

High-Sensitivity RT-LAMP Assay Enables Rapid, Field-Deployable Detection of Candidatus Liberibacter Asiaticus in Crude DNA Extracts from Citrus Phyllosphere and Psyllid Vectors - Ummad ud Din Umar; Syed Muhammad Zaka; Muhammad Nauman Tahir; Muhammad Kashif; Ateeq Ur Rehman; Sagheer Atta; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Sodium benzoate, potassium sorbate, and natamycin levels in doogh from Sulaymaniyah, Kurdistan region of Iraq and health risk assessment - Shilan Muhammad Abdulla; Ramin Aslani; Mohammad Hasan Zarghi; Parisa Sadighara; Ayub Ebadi Fathabad (Food Additives & Contaminants Part B-Surveillance, 2025)

Neuroprotective potential of the methanolic leaf extract of Cheilanthes tenuifolia in Swiss albino mice - Asraful Islam Rakib; Raihan Chowdhury; Md. Shimul Bhuia; Md. Sakib Al Hasan; Rubel Hasan; Siddique Akber Ansari; Irfan Aamer Ansari; Sarfaraz Ahmed; John Eversong Lucena de Vasconcelos; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (South African Journal of Botany, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Salvianolic acid A enhances sedative effect of diazepam through the GABAergic pathway: In vivo, molecular docking, and pharmacokinetics approaches - Imam Hossen Rakib; Mohd Shahnawaz Khan; Arusha Ayub; Md. Sakib Al Hasan; Mohammed Alfaifi; Md. Shimul Bhuia; Emon Mia; Noshin Tasnim Yana; Md. Nasimul Haque Shipon; Muhammad Torequl Islam (Neurotoxicology and Teratology, 2025)

Evaluation of the Diametrical Core Deformation Analysis (DCDA) and Fracture Surface Morphology for In-Situ Stress Estimation - Qingsen Meng; Yanjun Shang; Jianjun Chi; Shengwen Qi; Muhammad Hasan; Xuetao Yi (Rock Mechanics and Rock Engineering, 2025)

Assessments of protodioscin’s antinociceptive and antidiarrheal properties: in vivo and in silico investigations on macromolecule binding affinity and modulatory effects - Pompa Rani Ghosh; Md. Sakib Al Hasan; Razina Rouf; Raihan Chowdhury; Balkrishnan Yadav; Emon Mia; Md. Tanvir Islam; Md. Rakibul Hasan; Siddique Akber Ansari; Irfan Aamer Ansari; Md. Shimul Bhuia; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploration and evaluation of antioxidant activity in isolated phenolics from Jasminum scandens (retz) vahl - Afsin Malik; Faria Mannan Mithi; Sania Ashrafi; Muhammad Abdullah Al-Mansur; Monira Ahsan; Choudhury Mahmood Hasan; A.T.M. Zafrul Azam (Natural Product Research, 2025)

Memory-Enhancing Effects of Dauricine in Swiss Mice: Possible Molecular Interventions Through In Vivo and In Silico Studies - Md. Showkot Akbor; Md. Sakib Al Hasan; Mst. Farjanamul Haque; Zakir Husain; Md. Tahajul Islam; Md. Samim Hossen; Md. Shadin; Shoyaeb Ahammed; Noshin Tasnim Yana; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (NeuroMolecular Medicine, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

The heat shock matters with specific attention to the expression of Hsp60 under thermal stress in fish: A critical review - Md Toasin Hossain Aunkor; Mohammad Mehedi Hasan Khan; Muhammad Anamul Kabir; Md Topu Raihan; Md Faruque Miah (Ecological Genetics and Genomics, 2025)

Silicon-mediated Nutrient Deterrence Could Reduce Aphid (Brevicoryne brassicae L.) Abundance and Improve Crop Yield by Eliciting Phenolic Defense in Canola (Brassica napus L.) - Muhammad Wajid Javed; Mansoor-ul -Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Journal of Soil Science and Plant Nutrition, 2025)

Amendment of Tomato (Lycopersicon esculentum L.) Grown in Calcareous Soil with Spent Mushroom Substrate-derived Biochar: Improvement of Morphological, Biochemical, Qualitative Attributes, and Antioxidant Activities - Hasan Sardar; Muhammad Waqas; Aamir Nawaz; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Ayman A. Ghfar; Saikh M. Wabaidur; Sami Abou Fayssal (Journal of Soil Science and Plant Nutrition, 2025)

Marine landscape mapping for ecologically relevant habitat suitability modelling - Bryan Yong; Khaira Ismail; Azizi Ali; Rozaimi Che Hasan; Muhammad Abdul Hakim Muhamad (Earth Science Informatics, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Induced resistance and nutrient deterrence reduce aphid reproduction and improve crop yield, phenolic defense, and economic benefits of canola (Brassica napus L.) in the field - Muhammad Wajid Javed; Mansoor-Ul-Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2025)

Harvest Time Influences Quality and Storability of ‘Chandler’ Strawberries Grown Under Subtropical Conditions of Pakistan - Ayesha Maryam; Raheel Anwar; Mahmood Ul Hasan; Sajid Ali; Ahmad Sattar Khan; Muhammad Moaaz Ali; Khurram Ziaf (Applied Fruit Science, 2025)

Digital twins: cornerstone to circular economy and sustainability goals - Zain Anwar Ali; Mahreen Zain; Raza Hasan; Muhammad Salman Pathan; Hussain AlSalman; Faisal Abdulaziz Almisned (Environment, Development and Sustainability, 2025)
Accurate information is a prerequisite for circulation and greater longevity of materials and products, enabling the economically and environmentally successful transition of circular economy (CE) in the aspiration towards sustainable development. However, a lack of appropriate digital tools is noticed in supplying relevant information and supporting recyclability, reusability, and reducibility processes. This study focuses on a building block of evolving technologies anointed the digital twin (DT). It aims to conceptualize DT as a cornerstone for the CE paradigm, positively influencing sustainability. It also endeavors to scrutinize remarkable implementations of DT-driven CE, accomplishing sustainable development goals (SDGs) in Ireland. An iterative methodology based on four steps is adopted to review an explosion of relevant, recent literature published in 2019–2024 and multiple case studies of Irish construction and manufacturing sectors. By analyzing the literature, this study discovers the evolution and taxonomy of DT, other technologies essential for its deployment, its proactive role in implementing CE and SDGs, and some challenges. Key findings of case studies reveal the current trajectory of employing DT with other digital products, upholding the CE practices within the bounds of the SDGs in Irish companies. In conclusion, DT is a conceivable means for advancing CE solutions and attaining SDGs towards social, economic, and environmental sustainability. The implications of this study are both theoretically and practically significant, encouraging industrialists and academia to adopt DT. It will help scholars gain a thorough understanding and guide industrialists to downsize their carbon footprint and waste, accomplishing SDGs. It will inspire managers with DT-driven information for decision-making and facilitate government and policymakers to collaborate in designing essential policies. Graphical Abstract

Anticancer activity of Jasminum sambac and its bioactive phytochemicals against the PI3K-AKT-mTOR pathway: A literature-based in silico study - Md. Sakib Al Hasan; Md. Shimul Bhuia; Raihan Chowdhury; Md. Shadin; Emon Mia; Noshin Tasnim Yana; Imam Hossen Rakib; Siddique Akber Ansari; Irfan Aamer Ansari; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (South African Journal of Botany, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

The regulatory role of phytohormones in plant drought tolerance - Zhenqi Liao; Beibei Chen; Hatem Boubakri; Muhammad Farooq; Luis Alejandro Jose Mur; Daisuke Urano; Chee How Teo; Boon Chin Tan; MD Mahadi Hasan; Mehtab Muhammad Aslam; Muhammad Yahya Tahir; Junliang Fan (Planta, 2025)

Unveiling the anxiolytic and analgesic effects of citronellal in Swiss mice: in vivo and in silico insights into COX and GABAA receptor pathways - Muhammad Torequl Islam; Md. Sakib Al Hasan; Raihan Chowdhury; Emon Mia; Imam Hossen Rakib; Noshin Tasnim Yana; Heba A. S. El-Nashar; Siddique Akber Ansari; Irfan Aamer Ansari; Md. Amirul Islam; Zainab M. Almarhoon; William N. Setzer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Combined effects of ternary oxides (Mg-Cu-O) and jute stick derived activated carbon for hydrogen storage in MgH2 - Mehedi Hasan; Deboshree Rani Mukta; Abdullah Mohammad Sarjish; Stefano Enzo; Muhammad Nurunnabi Siddiquee; Mohammad Mozahar Hossain; Victoria Padilla; Mohammed Jasim Uddin; Wasikur Rahman (Environmental Science and Pollution Research, 2025)

Exploring omics solutions to reduce micro/nanoplastic toxicity in plants: A comprehensive overview - Samia Muhammad Arif; Ilham Khan; Muhammad Saeed; Sunbal Khalil Chaudhari; Mansour Ghorbanpour; Murtaza Hasan; Ghazala Mustafa (Science of The Total Environment, 2025)

A fuzzy decision-making model for enhancing sustainable tourism investments in climate-vulnerable destinations - Muhammad Shahbaz; Serhat Yüksel; Serkan Eti; Hasan Dinçer; Shoh-Jakhon Khamdamov (Journal of Environmental Management, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Gigantol, a promising natural drug for inflammation: a literature review and computational based study - Raihan Chowdhury; Shimul Bhuia; Asraful Islam Rakib; Sakib Al Hasan; Manik Chandra Shill; Heba A. S. El-Nashar; Mohamed El-Shazly; Muhammad Torequl Islam (Natural Product Research, 2025)

Identify the potential pathways and candidate biomarkers of stroke associated with bipolar disorder: Bioinformatics and system biology approach - Md. Faruk Hosen; Md. Abul Basar; Mst. Farjana Yasmin; Md. Rakibul Hasan; Muhammad Shahin Uddin (Journal of Proteins and Proteomics, 2025)

Fostering managers’ hope: A multi-analysis perspective on how green initiatives drive organizational performance - Mohd Adil; Syed Muhammad Fazel-e-Hasan; Hormoz Ahmadi; Mohd Sadiq; Harjit Sekhon; Alireza Amrollahi (Journal of Cleaner Production, 2025)

Modified atmosphere packaging and melatonin application alleviates chilling injury in ‘Fuyu’ persimmon fruit by reducing ethylene production, mitigating ROS accumulation, and maintaining antioxidant system - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Andrew Woodward; Eben Afrifa- Yamoah (Food Packaging and Shelf Life, 2025)

Plants breathing under pressure: mechanistic insights into soil compaction-induced physiological, molecular and biochemical responses in plants - Md. Mahadi Hasan; Xu-Dong Liu; Md Atikur Rahman; Yehia Hazzazi; ·Muhammad Wassem; Shantwana Ghimire; Nadiyah M. Alabdallah; Basmah M. Alharbi; Ahmad Humayan Kabir; Guangqian Yao; Xiang-Wen Fang (Planta, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

Fungicide resistance in Fusarium species: exploring environmental impacts and sustainable management strategies - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Muhammad Shahbaz; Aqleem Abbas; Fahad Hakim; Muhammad Shabbir; Yee Shin Tan; Jaya Seelan Sathiya Seelan (Archives of Microbiology, 2025)

Enhancing the performance of Litopenaeus vannamei nursery and grow-out by modifying Mg/Ca ratios in biofloc systems using low-salinity groundwater of Kuwait Desert - Sherain N. Al-Subiai; In Kwon Jang; Sun-Hye Bae; Hong-seok Yoon; Sumaiah Hussain; Sabeekah AlNuaimi; Muhammad Al-Foudari; Enas Al-Hasan (Aquaculture, 2025)

Preharvest methyl jasmonate application delays cell wall degradation and upregulates phenolic metabolism and antioxidant activities in cold stored raspberries - Hafiz Muhammad Shoaib Shah; Zora Singh; Mahmood Ul Hasan; Andrew Woodward; Eben Afrifa-Yamoah (Food Chemistry, 2025)

Sorghum starch review: Structural properties, interactions with proteins and polyphenols, and modification of physicochemical properties - Muhammad Luthfan Haziman; Muhammad Iskandar Ishaq; Muhammad Abdillah Hasan Qonit; Endang Gati Lestari; Pepi Nur Susilawati; Wiwi Widarsih; Cheppy Syukur; Heny Herawati; Ramlah Arief; Budi Santosa; Resmayeti Purba; Robi Andoyo; et al. (Food Chemistry, 2025)

Assessment of clot-lysing and membrane-stabilizing activity of gallic acid through cyclooxygenase-1 and plasminogen interaction pathways - Shriti Raj Kumari Sah; Md Sakib Al Hasan; Lalan Kumar Thakur; Md Shadin; Raihan Chowdhury; Shoyaeb Ahammed; Siddique Akber Ansari; Irfan Aamer Ansari; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Food Bioscience, 2025)

The Impact of Acid Strength and Mineral Composition on Spontaneous Imbibition with Reactive Fluids - Muhammad Andiva Pratama; Hasan Javed Khan (Transport in Porous Media, 2025)
Capillary rise experiments are conducted in a set of calcareous and siliceous rocks with varying mineralogy and petrophysical properties to understand the coupled impact of reactivity and spontaneous imbibition. A capillary rise experiment is performed in each sample: first with deionized water, then with a dilute acidic solution, and finally again with deionized water, and the capillary rise profile for each is recorded. Pre- and post-acid petrophysical properties such as porosity, permeability, pore size distribution, and contact angle are measured for each sample. The mineral makeup of the rocks significantly influences how the acidic fluids penetrate the samples. The primary reactions are the dissolution of Ca- and Mg-rich minerals which alter the pore network. The higher acid strength results in higher capillary rise in calcareous rocks and results in an increase in the average pore size. The same pH acid results in lower capillary rise in the siliceous rocks, and a general decrease in the average pore size is observed. Changes in contact angle indicate increased water affinity in carbonate and reduced affinity in sandstone. The link between capillary interactions and fluid reactivity is often overlooked in fluid flow studies, and this research sheds light on the importance of reactivity during spontaneous imbibition, offering insights into dissolution and precipitation processes during capillary flow.

Methyl Jasmonate Application Downregulates Drupelet Reversion and Enhances Phenolic Biosynthesis and Antioxidant Potential of Blackberries - Hafiz Muhammad Shoaib Shah; Zora Singh; Mahmood Ul Hasan; Jashanpreet Kaur; Eben Afrifa-Yamoah; Andrew Woodward (Journal of Plant Growth Regulation, 2025)
Blackberry plants were sprayed with methyl jasmonate (MJ 0, 1, 2 or 3 mmol L −1 ), 2 weeks before tentative harvest maturity, to evaluate its influence on red drupelet reversion (RDR), antioxidant capacity and postharvest quality during cold storage up to 12 days. MJ significantly reduced RDR and weight loss while maintaining higher anthocyanins and flavonoids during cold storage for 12 days. MJ application upregulated phenolic metabolism by maintaining higher phenylalanine ammonia lyase activity, and showed higher total antioxidants, ascorbic acid, and glutathione content. MJ-treated blackberries displayed higher activities of superoxide dismutase, catalase, ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase and glutathione reductase enzymes, than control for 12 days of cold storage. Moreover, MJ-treated fruit suppressed the production of hydrogen peroxide radicals and malondialdehyde with lower activities of polyphenol oxidase and lipoxygenase enzymes. In conclusion, preharvest application of MJ has the potential to reduce RDR, improve antioxidant capacity and maintain fruit quality of cold stored blackberries.

Assessing the Effectiveness of Audio-Visual vs. Visual Neurofeedback for Attention Enhancement: A Pilot Study with Neurological, Behavioural, and Neuropsychological Measures - Osama Ejaz; Muhammad Abul Hasan; Faryal Raees; Maham Hammad; Saad Ahmed Qazi (Brain Topography, 2025)

Implications of Microalgal–Bacterial Interactions in Modern Aquaculture Practices: A Review of the Current Knowledge - Sardar Ali; Waqas Waqas; Md. Akibul Hasan Bakky; Sahib Zada; Uddin Md Saif; Md Tawheed Hasan; Muhammad Shafiq; Tariq Dildar; Wang Hui (Reviews in Aquaculture, 2025)
Microalgae play a crucial role in aquaculture due to their nutritional value and antimicrobial properties, yet harvesting them can be energy intensive. To address this, microalgal–bacterial interactions have emerged as a sustainable approach, enhancing growth rates and wastewater treatment efficiency but also significantly improve nutrient cycling, particularly through the removal of ammonia and phosphorus. These interactions range from mutualism to antagonism, influencing nutrient exchange and ecological niche formation. Despite their potential, the integration of bacterial–microalgal consortia remains limited in aquaculture. This review aims to expand understanding of these interactions, their benefits, and their role in optimizing aquaculture systems. Various aspects of microalgae–bacterial interactions, including mutualistic and commensal relationships, antibiotics production by algae, and the algicidal role of bacteria, are discussed. Factors influencing these interactions, such as nutrient availability, the physical environment, chemical signaling, and microbial community composition, are also explored. The potential effects of microalgae–bacterial interactions on aquaculture, including enhanced revenue, efficiency, and ecological sustainability, are highlighted. Further research is needed to identify bacterial groups' influence on microalgal output and their potential for enhancing productivity in commercial aquaculture systems. Understanding and leveraging these microbial interactions could significantly improve aquaculture practices.

Depositional and diagenetic controls on the reservoir quality of marginal marine sandstones: An example from the Early Devonian subbat member, jauf formation, northwest Saudi Arabia - Anas Muhammad Salisu; Hasan Algheryafi; Abdulwahab Muhammad Bello; Abduljamiu O. Amao; Bandar Al-Otaibi; Khalid Al-Ramadan (Marine and Petroleum Geology, 2024)

Tangeretin exerts and modulates the anxiolytic effects of the GABAkine drugs diazepam and flumazenil in mice: Molecular interventions through animal behavior and molecular dynamic simulations - Zakir Husain; Md Saifiuzzaman; Md Shimul Bhuia; Jannatul Ferdous; Md Sakib Al Hasan; Mehedi Hasan Bappi; Md Showkot Akbor; Siddique Akber Ansari; Irfan Aamer Ansari; Md Amirul Islam; Muhammad Torequl Islam (Food Bioscience, 2024)

Wood biochar induced metal tolerance in Maize (Zea mays L.) plants under heavy metal stress - Atiqa Zahra; Sadaf Kayani; Asim Shahzad; Tijen Demiral Sert; Hasan Ozcelik; Mingzhou Qin; Muhammad Naeem; Motsim Billah (Environmental Research, 2024)

Drought Priming Enhanced Grain Yield of Wheat Against Salinity Stress - Ashutus Singha; Jahidul Karim; Asif Adnan Prince; Nargis Akter; khalada Akter Runa; Muhammad Naqib; A. K. Mohibul Islam; Setu Roy; Jouadul Hasan (Water Conservation Science and Engineering, 2024)

Role of exogenous silica fertilization and genotype selection in attenuating oxidative and osmotic stress in wheat (Triticum aestivum L.) under water deficit conditions - Muhammad Anwar ul Haq; Muhammad Nadeem; Munaza Naseem; Ghulam Hasan Abbasi; Muhammad Ali; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Tayyab Mehmood; Muhammad Awais; Rizwan Ullah; Tasawar Ali (Plant and Soil, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

Pangenome analysis of five representative Tropheryma whipplei strains following multiepitope-based vaccine design via immunoinformatic approaches - Ahmad Hasan; Muhammad Ibrahim; Wadi B. Alonazi; Rongrong Yu; Bin Li (Molecular Genetics and Genomics, 2024)

Towards smart and sustainable transportation: the role of artificial intelligence and new technologies in mitigating passenger car CO2 emissions in European countries - Walid Chatti; Muhammad Tariq Majeed; Haitham Khoj; Mahadi Hasan Miraz; Amanat Ali (Environment, Development and Sustainability, 2024)

Occurrence, characteristics and distribution of microplastics in commercial marine fishes of the Bay of Bengal - Pronoy Mondal; Md. Sazedul Hoque; Md. Arifur Rahman; Md. Mahmudul Hasan; Suprakash Chakma; Muhammad Saiful Islam; Md. Shahjahan (Marine Pollution Bulletin, 2024)

Trans-Ferulic acid reduces the sedative activity of diazepam in thiopental sodium-induced sleeping mice: A potential GABAergic transmission - Md. Shimul Bhuia; Md. Sakib Al Hasan; Raihan Chowdhury; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (Neurotoxicology and Teratology, 2024)

Methyl jasmonate advances fruit ripening, colour development, and improves antioxidant quality of ‘Yoho’ and ‘Jiro’ persimmon - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Andrew Woodward; Eben Afrifa-Yamoah (Food Chemistry, 2024)

Estimation of Young’s modulus for rocks using a non-invasive CSAMT method - Muhammad Hasan; Yanjun Shang; Qingyun Di; Qingsen Meng (Bulletin of Engineering Geology and the Environment, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Carbohydrate structural complexity modulates the formation, composition and functionality of microbial flocs and its impact on gut microbiota and growth of Pacific white shrimp - Julie Ekasari; Muhammad Faris Allam; Wiyoto Wiyoto; Pande Gde Sasmita Julyantoro; Ichsan Ahmad Fauzi; Muhamad Gustilatov; Hasan Nasrullah (Aquaculture, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Longitudinal Morphometric Changes in the Corticospinal Tract Shape After Hemorrhagic Stroke - Seth B. Boren; Sean I. Savitz; Nicole Gonzales; Khader Hasan; Andrea Becerril-Gaitan; Vahed Maroufy; Yuan Li; James Grotta; Emily A Steven; Ching-Jen Chen; Clark W. Sitton; Jaroslaw Aronowski; et al. (Translational Stroke Research, 2024)

Flaxseed mucilage—a green additive for the enhancement of water-based mud system characteristics - Faiza Kanwal; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney; Muhammad Ovais Tariq; Leena Hasan Ahmed; Umer Ahmed Khan; Aashan Sheikh; Muhammad Salman (Arabian Journal of Geosciences, 2024)

Health risk assessment of bread wheat grown under cadmium and nickel stress and impact of silicic acid application on its growth, physiology, and metal uptake - Alina Shafiq; Muhammad Emmad Munawar; Muhammad Nadeem; Asia Khan; Ghulam Hasan Abbasi; Muhammad Anwar ul Haq; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Application of deep learning for livestock behaviour recognition: A systematic literature review - Ali Rohan; Muhammad Saad Rafaq; Md. Junayed Hasan; Furqan Asghar; Ali Kashif Bashir; Tania Dottorini (Computers and Electronics in Agriculture, 2024)

Batch Electrocoagulation Process for the Removal of High Colloidal Clay from Open-Cast Coal Mine Water Using Al and Fe Electrodes - Muhammad Sonny Abfertiawan; Mindriany Syafila; Marisa Handajani; Faiz Hasan; Hanifah Oktaviani; Firman Gunawan; dan Febriwiadi Djali (Mine Water and the Environment, 2024)
Open-cast coal mining operations can produce water with high amounts of total suspended solids (TSS). We tested the use of electrocoagulation for the removal of colloidal clay from mine water. Monopolar batch electrocoagulation was performed at the laboratory scale using Al and Fe electrodes and varying the DC current (0.5, 1, and 2 A) and contact time (15, 30, and 45 min). Aluminum electrode electrocoagulation with a current of 2 A and a contact time of 15 min had the greatest TSS removal efficiency (99%), with concentrations decreasing from 5,400 to 23 mg/L. The greatest removal (98 and 99%, respectively) was obtained using an Al electrode with an electric current of 0.5 and 1 A, with 30 min of contact time. With an Fe electrode, the greatest efficiency was achieved with a current of 2 A and a contact time of 30 min. The TSS removal efficiency reached 98% while the concentration dropped to 66 mg/L, followed by 89% and 95% for the 0.5 A-45 min and 1 A-15 min variations, respectively.

Modeling and monitoring cotton production using remote sensing techniques and machine learning: a case study of Punjab, Pakistan - Sher Shah Hasan; Muhammad Arif Goheer; Muhammad Uzair; Saba Fatima (Environment, Development and Sustainability, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Estimation of rock core indices for development of underground infrastructure using non-invasive geophysical methods - Muhammad Hasan; Yanjun Shang; Shengwen Qi; Qingsen Meng (International Journal of Rock Mechanics and Mining Sciences, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

Insights into phytonutrient profile and postharvest quality management of jackfruit: A review - Jashanpreet Kaur; Zora Singh; Hafiz Muhammad Shoaib Shah; Muhammad Sohail Mazhar; Mahmood Ul Hasan; Andrew Woodward (Critical Reviews in Food Science and Nutrition, 2024)

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Estimating economic losses from perceived heat stress in a global south country, Bangladesh - Mondira Bardhan; Muhammad Mainuddin Patwary; Sardar Al Imran; Sharif Mutasim Billah; Mehedi Hasan; Asma Safia Disha; Md Pervez Kabir; Chameli Saha; Md. Najmus Sayadat Pitol; Matthew H.E.M. Browning (Urban Climate, 2024)

Dual adoption opportunities and prospects for mining and industrial waste recovery through an integrated carbon capture, utilization and storage - Faradiella Mohd Kusin; Sharifah Nur Munirah Syed Hasan; Verma Loretta M. Molahid; Muhammad Hameer Soomro (Sustainable Production and Consumption, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Evaluating climate change impacts on reef environments via multibeam echosounder and Acoustic Doppler Current profiler technology - Mohd Azhafiz Abdullah; L.F. Chuah; Razak Zakariya; Asad Syed; Rozaimi Che Hasan; Shahrul Miza Mahmud; Abdallah M. Elgorban; A. Bokhari; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman (Environmental Research, 2024)

Enhancing drought tolerance in broccoli (Brassica oleracea L.) through melatonin application: Physiological and biochemical insights into growth, photosynthesis, and antioxidant defense mechanisms - Hasan Sardar; Muhammad Shafiq; Safina Naz; Sajid Ali; Riaz Ahmad; Shaghef Ejaz (Biocatalysis and Agricultural Biotechnology, 2024)

Testing the validity of pollution haven and pollution halo hypotheses in BRICMT countries by Fourier Bootstrap AARDL method and Fourier Bootstrap Toda-Yamamoto causality approach - Oguzhan Ozcelik; Hasan Bardakci; Abdulkadir Barut; Muhammad Usman; Narasingha Das (Air Quality, Atmosphere & Health, 2024)

Impact of extreme weather events on mental health in South and Southeast Asia: A two decades of systematic review of observational studies - Muhammad Mainuddin Patwary; Mondira Bardhan; Md Atiqul Haque; Syed Moniruzzaman; Johanna Gustavsson; Md Maruf Haque Khan; Jenni Koivisto; Marium Salwa; Saidur Rahman Mashreky; A.K.M. Fazlur Rahman; Anika Tasnim; Md Redwanul Islam; et al. (Environmental Research, 2024)

Advanced strategies to mitigate heavy metals in ground and sewage water - Muhammad Mahmood Ahmed; Tuba Tariq; Mirza Abid Mehmood; Muhammad Ashfaq; Murtaza Hasan (Current Opinion in Green and Sustainable Chemistry, 2024)

Comparative Assessment of Bioactive Compounds, Fruit Quality Attributes and Sugar Profiling in Early Maturing Table Grape (Vitis Vinifera L.) Cultivars from Pothohar, Pakistan - Muhammad Tahir Akram; Rashad Qadri; Muhammad Azam Khan; Arif Atak; Mehwish Liaquat; Tanveer Hussain; Muhammad Mumtaz Khan; Muhammad Azam; Mahmood ul Hasan (Applied Fruit Science, 2024)

Chemical element analysis of Arjuno-Welirang igneous rocks - Hanif ‘Izzuddin Zakly; Siti Zulaikah; Cahyo Aji Hapsoro; Shofi Maulida; Muhammad Fathur Rouf Hasan (Environmental Science and Pollution Research, 2024)

Evaluation of environmental impacts of cotton polo shirt production in Bangladesh using life cycle assessment - Shafiqul Islam; A.K.M. Mehedi Hasan; Muhammad Abdur Rahman Bhuiyan; Gajanan Bhat (Science of The Total Environment, 2024)

Bridging biological and food monitoring: A colorimetric and fluorescent dual-mode sensor based on N-doped carbon dots for detection of pH and histamine - Xiaoran Zhang; Jing Wang; Elias Hasan; Xincheng Sun; Muhammad Asif; Ayesha Aziz; Wenjing Lu; Chuan Dong; Shaomin Shuang (Journal of Hazardous Materials, 2024)

Effect of the number of Cyperus rotundus and medium height on the performance of batch-constructed wetland in treating aquaculture effluent - Muhammad Fauzul Imron; Wa Ode Ayu Hestianingsi; Trisnadi Widyaleksono Catur Putranto; Nita Citrasari; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Setyo Budi Kurniawan (Chemosphere, 2024)

Quantifying canopy nitrogen of Aman rice utilizing multi-temporal unmanned aerial systems - Maruf Hossain; Hasan Muhammad Abdullah; Tanvir Ahmmed; Md Giashuddin Miah; Moin Us Salam; Majharul Islam; Md Mizanur Rahman (Remote Sensing Applications: Society and Environment, 2024)

Technological advancements in water heating approaches for membrane distillation desalination process: From bulk to localized heating - Muhammad Usman Farid; Jehad A. Kharraz; Samriddhi Sharma; Rabia Jalil Khan; Noman Khalid Khanzada; Bhaskar Jyoti Deka; Manoj Kumar Nallapaneni; Shaurhat S. Chopra; Shao-Yuan Leu; Shadi W. Hasan; Nidal Hilal; Alicia K.J. An (Desalination, 2024)

Development of Maghemite Nanoparticles to Effectively Adsorb Methylene Blue Dye from Water - Muhammad Azeem Ashraf; Mumtaz Hasan Malik; Assad Farooq; Muhammad Tayyab Noman; Nayab Khan (Water, Air, & Soil Pollution, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Geophysical estimation of 2D hydraulic conductivity for groundwater assessment in hard rock - Qiang Gao; Muhammad Hasan; Yanjun Shang; Shengwen Qi (Acta Geophysica, 2024)

Removal of reactive dyes from textile industrial effluent using electrocoagulation in different parametric conditions of aluminum electrodes - Abdul Mannan Zafar; Asma Naeem; Muhammad Athar Minhas; Muhammad Jamal Hasan; Sania Rafique; Amir Ikhlaq (Total Environment Advances, 2024)

Sustainable hydrogen production via microalgae: Technological advancements, economic indicators, environmental aspects, challenges, and policy implications - Hafiz Muhammad Uzair Ayub; Muhammad Nizami; Muhammad Abdul Qyyum; Noman Iqbal; Ala'a.H. Al-Muhtaseb; Mudassir Hasan (Environmental Research, 2024)

Advancements in TiO2-based photocatalysis for environmental remediation: Strategies for enhancing visible-light-driven activity - Ruhma Rashid; Iqrash Shafiq; Muhammad Rehan Hasan Shah Gilani; Muhammad Maaz; Parveen Akhter; Murid Hussain; Kwang-Eun Jeong; Eilhann E. Kwon; Sungjun Bae; Young-Kwon Park (Chemosphere, 2024)

GCDN-Net: Garbage classifier deep neural network for recyclable urban waste management - Md Mosarrof Hossen; Azad Ashraf; Mazhar Hasan; Molla E. Majid; Mohammad Nashbat; Saad Bin Abul Kashem; Ali K. Ansaruddin Kunju; Amith Khandakar; Sakib Mahmud; Muhammad E.H. Chowdhury (Waste Management, 2024)

Histotoxicity induced by copper oxide nanoparticles (CuO-NPs) on developing mice (Mus musculus) - Munir Ahmad; Muhammad Khalil Ahmad Khan; Naveed Ahmad; Munazza Parveen; Khurram Shahzad; Ali Hasan (Food and Chemical Toxicology, 2024)

Antibacterial effects of quercetagetin are significantly enhanced upon conjugation with chitosan engineered copper oxide nanoparticles - Adeelah Alvi; Saif Alqassim; Naveed Ahmed Khan; Bushra Khatoon; Noor Akbar; Muhammad Kawish; Shaheen Faizi; Muhammad Raza Shah; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (BioMetals, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Melatonin application suppresses oxidative stress and maintains fruit quality of cold stored ‘Esperanza’ raspberries by regulating antioxidant system - Hafiz Muhammad Shoaib Shah; Zora Singh; Mahmood Ul Hasan; Jashanpreet Kaur; Eben Afrifa-Yamoah; Andrew Woodward (Postharvest Biology and Technology, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Determination of microplastic pollution in marine ecosystems and its effective removal using an advanced nanobubble flotation technique - Jehad A. Kharraz; Mingyi Jia; Muhammad Usman Farid; Noman Khalid Khanzada; Nidal Hilal; Shadi W. Hasan; Alicia Kyoungjin An (Journal of Water Process Engineering, 2024)

Unraveling the impact of eco-centric leadership and pro-environment behaviors in healthcare organizations: Role of green consciousness - Ali Hasan; Xiang Zhang; Di Mao; Muhammad Kashif; Farhan Mirza; Rabia Shabbir (Journal of Cleaner Production, 2024)

The path of microplastics through the rare biodiversity estuary region of the northern Bay of Bengal - Al-Nure Mubin; Abu Reza Md. Towfiqul Islam; Mehedi Hasan; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Sha Alam; Md. Refat Jahan Rakib; Muhammad Saiful Islam; Nasima Momtaz; Venkatramanan Senapathi; Abubakr M. Idris; et al. (Journal of Contaminant Hydrology, 2024)

Evaluation of occupational health and safety intervention for the waste and sanitation workers in Bangladesh during COVID-19 - Dewan Muhammad Shoaib; Tanvir Ahmed; Kazy Farhat Tabassum; Mehedi Hasan; Fazle Sharior; Mahbubur Rahman; Makfie Farah; Md Azizur Rahman; Alauddin Ahmed; James B. Tidwell; Mahbub-Ul Alam (International Journal of Hygiene and Environmental Health, 2024)

The application of multi-attribute decision making methods in integrated watershed management - Rana Muhammad Adnan Ikram; Sarita Gajbhiye Meshram; Mohd Abul Hasan; Xinyi Cao; Ehsan Alvandi; Chandrashekhar Meshram; Saiful Islam (Stochastic Environmental Research and Risk Assessment, 2024)

Direct oral anticoagulants and the risk of adverse clinical outcomes among patients with different body weight categories: a large hospital-based study - Ezekwesiri Michael Nwanosike; Hamid A. Merchant; Wendy Sunter; Muhammad Ayub Ansari; Barbara R. Conway; Syed Shahzad Hasan (European Journal of Clinical Pharmacology, 2024)
Objective Through predictable pharmacokinetics—including a convenient fixed-dose regimen, direct oral anticoagulants (DOACs) are preferred over previous treatments in anticoagulation for various indications. However, the association between higher body weight and the risk of adverse consequences is not well studied among DOAC users. We aim to explore the association of body weight and adverse clinical outcomes in DOAC users. Methods A total of 97,413 anonymised DOAC users in a tertiary care setting were identified following structured queries on the electronic health records (EHRs) to extract the feature-rich anonymised dataset. The prepared dataset was analysed, and the features identified with machine learning (ML) informed the adjustments of covariates in the multivariate regression analysis to examine the association. Kaplan–Meier analysis was performed to evaluate the mortality benefits of DOACs. Results Among DOAC users, the odds of adverse clinical outcomes, such as clinically relevant non-major bleeding (CRNMB), ischaemic stroke, all-cause mortality, and prolonged hospital stay, were lower in patients with overweight, obesity, or morbid obesity than in patients with normal body weight. The odds of ischaemic stroke (OR 0.42, 95% CI: 0.36–0.88, p = 0.001) and all-cause mortality (OR 0.87, 95% CI: 0.81–0.95, p = 0.001) were lower in patients with morbid obesity than in patients with normal body weight. In the Kaplan–Meier analysis, apixaban was associated with a significantly lower rate of mortality overall and in obesity and overweight subgroups than other DOACs ( p < 0.001). However, rivaroxaban performed better than apixaban in the morbid obesity subgroup ( p < 0.001). Conclusion This study shows the positive effects of DOAC therapy on clinical outcomes, particularly in patients with high body weight. However, this still needs validation by further studies particularly among patients with morbid obesity.

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Oxalic acid: A blooming organic acid for postharvest quality preservation of fresh fruit and vegetables - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Jashanpreet Kaur; Andrew Woodward; Eben Afrifa-Yamoah; Aman Ullah Malik (Postharvest Biology and Technology, 2023)

Therapeutic potentials of ononin with mechanistic insights: A comprehensive review - Md. Shimul Bhuia; Mst Asma Aktar; Raihan Chowdhury; Jannatul Ferdous; Md Anisur Rahman; Md Sakib Al Hasan; Muhammad Torequl Islam (Food Bioscience, 2023)

Revolutionizing wastewater treatment with microalgae: Unveiling resource recovery, mechanisms, challenges, and future possibilities - Hassimi Abu Hasan; Mohd Hafizuddin Muhamad; Bin Ji; Nur Aisyah Nazairi; Koh Weng Jiat; Saffi Irdina Sim Wan Azlan Sim; Amir Fitri Muhammad Shafiq Poh (Ecological Engineering, 2023)

Petrophysical properties evaluation and reservoir characterization of a giant gas field: Bangladesh case study - Mehedi Hasan; Bineta Mondol; Litao Chen; Muhammad Wajid Manzoor (Arabian Journal of Geosciences, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Policies and regulations for solar photovoltaic end-of-life waste management: Insights from China and the USA - Amjad Ali; Sheraz Alam Malik; Md Shafiullah; Muhammad Zeeshan Malik; Md Hasan Zahir (Chemosphere, 2023)

Long-term quantification of pre and post-monsoon surface water area of Bangladesh - Syed Muhimeen Ahmed; Hasan Muhammad Abdullah; Tahsin Tanha Chowdhury; Abiar Rahman; Mohammad Zahangeer Alam (Remote Sensing Applications: Society and Environment, 2023)

Groundwater vulnerability assessment to pollution using GIS-based DRASTIC and GOD methods in Araihazar upazila of Narayanganj district, Bangladesh - Muhammad Abu Sayed; A.S.M. Maksud Kamal; Abrar Hossain; Mahmudul Hasan; Mahfuzur R Khan; Kazi Matin Uddin Ahmed; Peter S.K. Knappett (Groundwater for Sustainable Development, 2023)

Antiemetic effects of sclareol, possibly through 5-HT3 and D2 receptor interaction pathways: In-vivo and in-silico studies - Mehedi Hasan Bappi; Abdullah Al Shamsh Prottay; Khattab Al-Khafaji; Md Showkoth Akbor; Muhammad Kamal Hossain; Md Shahazul Islam; Afia Ibnath Asha; Cassio Rocha Medeiros; Catarina Martins Tahim; Elaine Cristina Pereira Lucetti; Henrique Douglas Melo Coutinho; Hossam Kamli; et al. (Food and Chemical Toxicology, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

The role of environmental regulation and green human capital towards sustainable development: The mediating role of green innovation and industry upgradation - Likun Ni; Sayed Fayaz Ahmad; Talal Obaid Alshammari; Haoshen Liang; Ghadeer Alsanie; Muhammad Irshad; Randah Alyafi-AlZahri; Rima H. BinSaeed; Mohammed Hasan Ali Al-Abyadh; Sahar Moh'd Mahmood Abu Bakir; Ahmad Y.A. Bani Ahmad Ayassrah (Journal of Cleaner Production, 2023)

Anxiolytic-like effect of succinic acid: A possible GABAergic intervention - Md. Nayem Mia; Shanita Zaman Smrity; Mehedi Hasan Bappi; Hossam Kamli; Tawhida Islam; Abdullah Al Shamsh Prottay; Md. Showkoth Akbor; Md. Abdul Latif; Shoriful Islam; Kushal Bhakta; Manik Chandra Shill; Francisco Claudeni Pereira de Sousa; et al. (Food Bioscience, 2023)

Genome-wide analysis and expression profiling of YUCCA gene family associated with plant vigor in Japanese apricot (prunus mume Sieb. Et zucc) - Faisal Hayat; Yang Bai; Shahid Iqbal; Chengdong Ma; Muhammad Moaaz Ali; Muhammad Adnan Shahid; Mahmood Ul Hasan; Walid F. A. Mosa; Ummara Khan; Huang Xiao; Zhihong Gao (Horticulture, Environment, and Biotechnology, 2023)

Artificial neural network and decision tree–based models for prediction and validation of in vitro organogenesis of two hydrophytes—Hemianthus callitrichoides and Riccia fluitans - Esra Özcan; Hasan Hüseyin Atar; Seyid Amjad Ali; Muhammad Aasim (In Vitro Cellular & Developmental Biology - Plant, 2023)

Comparative appraisal of groundwater quality in lower and upper riparians of Malir River system through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Aamir Alamgir; Adnan Khan; Muhammad Arsalan (Arabian Journal of Geosciences, 2023)

Preharvest melatonin application alleviates red drupelet reversion, improves antioxidant potential and maintains postharvest quality of ‘Elvira’ blackberry - Hafiz Muhammad Shoaib Shah; Zora Singh; Mahmood Ul Hasan; Eben Afrifa-Yamoah; Andrew Woodward (Postharvest Biology and Technology, 2023)

Hydrolyzed polyacrylonitrile UF-membrane for surface and TAP water treatment: Influence on DBPs formation and removal - Muhammad Saboor Siddique; Qingyun Song; Xuejun Xiong; Hasan Fareed; Nigel Graham; Wenzheng Yu (Chemical Engineering Journal, 2023)

Melatonin Mitigates Salt-Induced Growth Inhibition Through the Regulation of Carbohydrate and Nitrogen Metabolism in Tomato Seedlings - Mohammad Shah Jahan; Guihua Li; Dasen Xie; Reham Farag; Md. Mahadi Hasan; Nadiyah M. Alabdallah; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Muhammad Zeeshan; Jamal Nasar; Muhammad Ahsan Altaf; Md Atikur Rahman (Journal of Soil Science and Plant Nutrition, 2023)

Correction: Water hyacinth (Eichhornia crassipes) fractions potentially normalize the lead (Pb) poisoning and enhance in vitro thrombolysis - A. M. Abu Ahmed; Sarowar Jahan Khan; Nipun Mojumder; Farjana Sharmen; Md. Atiar Rahman; Muhammad Abu Bakar; J. M. Kamirul Hasan Chowdhury; Mohammad Ali Azadi (Advances in Traditional Medicine, 2023)

Phytochemical screening and evaluation of antioxidant, anti-inflammatory, antimicrobial, and membrane-stabilizing activities of different fractional extracts of Grewia nervosa (Lour.) Panigrahi - Mehanaz Islam; Abdullah Al Shamsh Prottay; Irin Sultana; Abdullah Al Faruq; Mehedi Hasan Bappi; Md. Showkoth Akbor; Afia Ibnath Asha; Md. Munnaf Hossen; Pedro Esau Macedo Machado; Inacio Jose Secundo Junior; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Food Bioscience, 2023)

Citrinin as a potential anti-cancer therapy: A comprehensive review - Ag-Anne P.M. de Menezes; Raí P.S. Aguiar; José V.O. Santos; Chandan Sarkar; Muhammad T. Islam; Antonio L. Braga; Mohammad M. Hasan; Felipe C.C. da Silva; Javad Sharifi-Rad; Abhijit Dey; Daniela Calina; Ana A.C. Melo-Cavalcante; et al. (Chemico-Biological Interactions, 2023)

Usage of the XGBoost and MARS algorithms for predicting body weight in Kajli sheep breed - Asim Faraz; Cem Tırınk; Hasan Önder; Uğur Şen; Hafiz Muhammad Ishaq; Nasir Ali Tauqir; Abdul Waheed; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Coagulation–flocculation of aquaculture effluent using biobased flocculant: From artificial to real wastewater optimization by response surface methodology - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah; Ahmad Razi Othman; Hassimi Abu Hasan (Journal of Water Process Engineering, 2023)

Applicability of machine learning techniques in predicting wheat yield based on remote sensing and climate data in Pakistan, South Asia - Sana Arshad; Jamil Hasan Kazmi; Muhammad Gohar Javed; Safwan Mohammed (European Journal of Agronomy, 2023)

A changing coastal ecosystem: Cox’s Bazar in southeastern coastal region of Bangladesh - Md. Giashuddin Miah; Md. Rafiqul Islam; Joyashree Roy; Md. Mezanur Rahman; Hasan Muhammad Abdullah (Environment, Development and Sustainability, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Exploring impacts of water-extractable organic matter on pre-ozonation followed by nanofiltration process: Insights from pH variations on DBPs formation - Muhammad Saboor Siddique; Hongbo Lu; Xuejun Xiong; Hasan Fareed; Nigel Graham; Wenzheng Yu (Science of The Total Environment, 2023)

Mapping environmental sustainability of knitted textile production facilities - Md. Shamsuzzaman; Md Mazedul Islam; H M Rakib Ul Hasan; Adnan Maroof Khan; Abu Sadat Muhammad Sayem (Journal of Cleaner Production, 2023)

Epidemiological survey of bovine gammaherpesvirus 4 (BoHV-4) infection in cattle and buffalo from Pakistan - Anees Khalid; Aayesha Riaz; Arfan Yousaf; Irtaza Hassan Khan; Saif Ur-Rehman; Muhammad Moaeen-ud-Din; Song Li; Congli Tang; Muhammad Ali Shah; Murtaz-ul-Hasan (Veterinary Research Communications, 2023)

Indoor thermal management of a public transport with phase change material (PCM) - Hasibuzzaman Mahmud; Mufrad Islam; Muhammad Ershad Jaman Khan; Dewan Hasan Ahmed (Energy, Ecology and Environment, 2023)

Estimating ground-level PM2.5 using subset regression model and machine learning algorithms in Asian megacity, Dhaka, Bangladesh - Abu Reza Md. Towfiqul Islam; Mohammed Al Awadh; Javed Mallick; Subodh Chandra Pal; Rabin Chakraborty; Md. Abdul Fattah; Bonosri Ghose; Most. Kulsuma Akther Kakoli; Md. Aminul Islam; Hasan Raja Naqvi; Muhammad Bilal; Ahmed Elbeltagi (Air Quality, Atmosphere & Health, 2023)

High prevalence of multiple antibiotic resistance in fermented food-associated lactic acid bacteria in Malaysia - Yuli Haryani; Nadrah Abdul Halid; Goh Sur Guat; Mahmud Ab Rashid Nor-Khaizura; Muhammad Asyraf Md Hatta; Suriana Sabri; Son Radu; Hanan Hasan (Food Control, 2023)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Finite-time active fault-tolerant attitude control for flexible spacecraft with vibration suppression and anti-unwinding - Muhammad Noman Hasan; Muhammad Haris; Shiyin Qin (Advances in Space Research, 2023)

Microplastics in facial cleanser: extraction, identification, potential toxicity, and continuous-flow removal using agricultural waste–based biochar - Muhammad Adli Hanif; Naimah Ibrahim; Farrah Aini Dahalan; Umi Fazara Md. Ali; Masitah Hasan; Ayu Wazira Azhari; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2023)

Prevalence and abundance of antibiotic-resistant genes in culturable bacteria inhabiting a non-polar passu glacier, karakorum mountains range, Pakistan - Sabir Nawaz; Muhammad Rafiq; Ian L. Pepper; Walter Q. Betancourt; Aamer Ali Shah; Fariha Hasan (World Journal of Microbiology and Biotechnology, 2023)

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology - Dipta Dey; Rajib Hossain; Partha Biswas; Priyanka Paul; Md. Aminul Islam; Tanzila Ismail Ema; Bibhuti Kumar Gain; Mohammad Mehedi Hasan; Shabana Bibi; Muhammad Torequl Islam; Md. Ataur Rahman; Bonglee Kim (Molecular Diversity, 2023)

Transmission efficiency of Cotton leaf curl Khokhran virus /Cotton leaf curl Multan betasatellite complex by two whitefly cryptic species in Pakistan - Muhammad Afzal; Shafqat Saeed; Hasan Riaz; Muhammad Ishtiaq; M. Habib ur Rahman (International Journal of Tropical Insect Science, 2023)

Modelling of geomorphological features of fluvial systems in Eromanga Basin and North Sea using 3D seismic attributes - Haris Ahmed Khan; Saifullah Abdul Qadir; Muhammad Jahangir Khan; Faraz Hasan Siddiqui; Mirza Saad Ahsan (Journal of Earth System Science, 2023)

Investigation of PT 58 and PEG-6000-based finned heat sinks for thermal management of electronics - Radhi Abdullah Lawag; Hafiz Muhammad Ali; Md Hasan Zahir; Bilal A. Qureshi (Journal of Cleaner Production, 2023)

Does human movement-induced airflow elevate infection risk in burn patient’s isolation ward? A validated dynamics numerical simulation approach - Huiyi Tan; Keng Yinn Wong; Mohd Hafiz Dzarfan Othman; Bemgba Bevan Nyakuma; Desmond Daniel Chin Vui Sheng; Hong Yee Kek; Wai Shin Ho; Haslenda Hashim; Meng Choung Chiong; Muhammad Afiq Zubir; Nur Haliza Abdul Wahab; Syie Luing Wong; et al. (Energy and Buildings, 2023)

Determination of rock quality designation (RQD) using a novel geophysical approach: a case study - Muhammad Hasan; Yanjun Shang; Xuetao Yi; Peng Shao; He Meng (Bulletin of Engineering Geology and the Environment, 2023)

Utilization of bottom ash waste as a granular column to enhance the lateral load capacity of soft kaolin clay soil - Muhammad Syamsul Imran Zaini; Muzamir Hasan; Wan Nursyafiqah Binti Wan Jusoh (Environmental Science and Pollution Research, 2023)

Phytotechnology for domestic wastewater treatment: Performance of Pistia stratiotes in eradicating pollutants and future prospects - Muhammad Fauzul Imron; Abiyyu Armijn Firman Firdaus; Zhiella Octabriani Flowerainsyah; Dzikro Rosyidah; Nurina Fitriani; Setyo Budi Kurniawan; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Yudha Gusti Wibowo (Journal of Water Process Engineering, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

High carbohydrate increases amylase, plasma glucose, and gene expression related to glycolysis in giant gourami Osphronemus goramy - Dian Novita Sari; Julie Ekasari; Hasan Nasrullah; Muhammad Agus Suprayudi; Alimuddin Alimuddin (Fish Physiology and Biochemistry, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Abundance, characteristics, and spatial–temporal distribution of microplastics in sea salts along the Cox’s Bazar coastal area, Bangladesh - Muhammad Saiful Islam; Md. Rashed Hasan; Zahidul Islam (Environmental Science and Pollution Research, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Spatial evaluation of precipitation patterns in the catchment area of Malir River during monsoon spells of 2019 through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Muhammad Arsalan; Shahid Naseem; Humaira Kanwal (Arabian Journal of Geosciences, 2022)

Plant-based coagulants/flocculants: characteristics, mechanisms, and possible utilization in treating aquaculture effluent and benefiting from the recovered nutrients - Mohammad Mohammad Alnawajha; Setyo Budi Kurniawan; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Ahmad Razi Othman (Environmental Science and Pollution Research, 2022)

Correction of a CD55 mutation to quantify the efficiency of targeted knock-in via flow cytometry - Md. Lutfur Rahman; Toshinori Hyodo; Muhammad Nazmul Hasan; Yuko Mihara; Sivasundaram Karnan; Akinobu Ota; Shinobu Tsuzuki; Yoshitaka Hosokawa; Hiroyuki Konishi (Molecular Biology Reports, 2022)

The effects of Ginsenosides on PI3K/AKT signaling pathway - Soudeh Ghafouri-Fard; Neda Balaei; Hamed Shoorei; Syed Muhammad Farid Hasan; Bashdar Mahmud Hussen; Seyedeh Fahimeh Talebi; Mohammad Taheri; Seyed Abdulmajid Ayatollahi (Molecular Biology Reports, 2022)
Ginsenosides belong to a group of steroid glycosides that are extracted from the plant genus Panax (ginseng). This plant has been used for a long time for the treatment of a variety of disorders in traditional medicine. Recent studies have assessed the biological impact of Ginsenosides in cell culture or animal models. Animal studies have shown their beneficial impacts in the remedy of pathological conditions in different tissues. The ameliorating effects of Ginsenosides in diverse pathogenic conditions can be attributed to their effects on the production of reactive oxygen species. These substances mainly affect the activity of AMPK/AKT and PI3K/AKT pathways. The beneficial effects of Ginsenosides have been appraised in diabetes-related complications, spinal cord injury, cerebral ischemia, myocardial ischemia, and other disorders which are associated with oxidative stress. Moreover, these substances have been shown to interfere with the pathologic conditions during carcinogenesis. In the current study, we explain these impacts in two distinct sections including non-neoplastic conditions and neoplastic conditions.

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Plant Growth and Fruit Quality Response of Strawberry is Improved After Exogenous Application of 24-Epibrassinolide - Muhammad Moaaz Ali; Raheel Anwar; Aman Ullah Malik; Ahmad Sattar Khan; Saeed Ahmad; Zahoor Hussain; Mahmood Ul Hasan; Mudassar Nasir; Faxing Chen (Journal of Plant Growth Regulation, 2022)

Phosphate solubilizing epilithic and endolithic bacteria isolated from clastic sedimentary rocks, Murree lower Himalaya, Pakistan - Imran Khan; Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Sumayya Zaman; Fariha Hasan (Archives of Microbiology, 2022)

Evaluation of Engineering Rock Mass Quality via Integration Between Geophysical and Rock Mechanical Parameters - Muhammad Hasan; Yanjun Shang; Peng Shao; Xuetao Yi; He Meng (Rock Mechanics and Rock Engineering, 2022)

Comparative toxic effects of Eucalyptus globulus L. (Myrtales: Myrtaceae) and its green synthesized zinc oxide nanoparticles (ZnONPs) against Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) - Muhammad Amir Siddique; Mansoor ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2022)

Biorational approach for management of whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae), on cotton crop - Muhammad Iqbal; Muhammad Jalal Arif; Shafqat Saeed; Mansoor ul Hasan; Nazir Javed (International Journal of Tropical Insect Science, 2022)

Biosurfactants and chemotaxis interplay in microbial consortium-based hydrocarbons degradation - Muhammad Ibrar; Salman Khan; Fariha Hasan; Xuewei Yang (Environmental Science and Pollution Research, 2022)

Enhanced ultraviolet-visible photocatalysis of RGO/equaixial geometry TiO2 composites on degradation of organic dyes in water - Jaafar Hasan; Jing Wang; Zhentao Wang; Muhammad Idrees; Saima Batool; Caiwei Zhang; Chuanguang Qin (Environmental Science and Pollution Research, 2022)

Photocatalytic degradation of methylene blue using polyaniline-based silver-doped zinc sulfide (PANI-Ag/ZnS) composites - Sidra Mazhar; Umair Yaqub Qazi; Nimra Nadeem; Muhammad Zahid; Abdul Jalil; Fareeda Khan; Iftikhar Ul-Hasan; Imran Shahid (Environmental Science and Pollution Research, 2022)

Site suitability for engineering-infrastructure (EI) development and groundwater exploitation using integrated geophysical approach in Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Bulletin of Engineering Geology and the Environment, 2022)

QbD Approach towards Robust Design Space for Flutamide/PiperineSelf-Emulsifying Drug Delivery System with Reduced Liver Injury - Mithun Saha; Pallabi Sikder; Aditi Saha; Sharha Shah; Sharmin Sultana; Tushar Emran; Ananna Banik; Zahidul Islam; Muhammad Saiful Islam; Shazid Md. Sharker; Hasan Mahmud Reza (AAPS PharmSciTech, 2022)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Genomic attributes and recent advances in detection of white spot syndrome virus in shrimp: a review - Md Nazmul Hossain; Tanjia Afrin Chowdhury; Mahmudul Hasan; Kazi Faizul Azim; Sayadatunnasa Jenny; Muhammad Fazle Rabbee; Md. Mahbubur Rahman; Saneya Risa Somana (Marine Biology Research, 2021)

Effects of selenium on the uptake of toxic trace elements by crop plants: A review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Jörg Rinklebe; Daniel C. W. Tsang; Filip M. G. Tack; Ghulam Hasan Abbasi; Afzal Hussain; Avanthi Deshani Igalavithana; Byung Cheon Lee; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2021)

Joint geophysical prospecting for groundwater exploration in weathered terrains of South Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Environmental Monitoring and Assessment, 2021)

Expression and characterization of rainbow trout Oncorhynchus mykiss recombinant myoglobin - Muhammad Mehedi Hasan; Hideki Ushio; Yoshihiro Ochiai (Fish Physiology and Biochemistry, 2021)

Understanding the neurological mechanism involved in enhanced memory recall task following binaural beat: a pilot study - Muhammad Danish Mujib; Muhammad Abul Hasan; Saad Ahmed Qazi; Aleksandra Vuckovic (Experimental Brain Research, 2021)
Binaural beat (BB) is a promising technique for memory improvement in elderly or people with neurological conditions. However, the related modulation of cortical networks followed by behavioral changes has not been investigated. The objective of this study is to establish a relationship between BB oscillatory brain activity evoked by stimulation and a behavioral response in a short term memory task. Three Groups A, B, and C of 20 participants each received alpha (10 Hz), beta (14 Hz), and gamma (30 Hz) BB, respectively, for 15 min. Their EEG was recorded in pre, during, and post BB states. Participants performed a digit span test before and after a BB session. A significant increase in the cognitive score was found only for Group A while a significant decrease in reaction time was noted for Groups A and C. Group A had a significant decrease of theta and increase of alpha power, and a significant increase of theta and decrease of gamma imaginary coherence (ICH) post BB. Group C had a significant increase in theta and gamma power accompanied by the increase of theta and gamma ICH post BB. The effectiveness of BB depends on the frequency of stimulation. A putative neural mechanism involves an increase in theta ICH in parieto-frontal and interhemispheric frontal networks.

Sewage wastewater reclamation with sand column filter and reduction of heavy metal accumulation in tomato and okra - Safina Naz; Muhammad Akbar Anjum; Shaghef Ejaz; Sajid Ali; Bushra Saddiq; Hasan Sardar; Sakeena Tul-Ain Haider (Environmental Science and Pollution Research, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Toxic element profile of ice cream in Bangladesh: a health risk assessment study - Palash Kumar Dhar; Arifa Naznin; Muhammad Sarwar Hossain; Md. Kamrul Hasan (Environmental Monitoring and Assessment, 2021)

Factors influencing the combined efficacy of microbial insecticides and inert dusts for the control of Trogoderma granarium - Rameesha Amjad Ali; Mansoor ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi; Amer Rasul (International Journal of Tropical Insect Science, 2021)

Surging trends in prescriptions and costs of antidepressants in England amid COVID-19 - Shahad A. Rabeea; Hamid A. Merchant; Muhammad Umair Khan; Chia Siang Kow; Syed Shahzad Hasan (DARU Journal of Pharmaceutical Sciences, 2021)
The social restrictions amid coronavirus disease 2019 (COVID-19) pandemic have posed a serious threat to mental health and have implications in the use of medications for mental health including antidepressants (ADs). This study investigated the trends in prescriptions and costs of various ADs in England during COVID-19 pandemic. National prescribing rates and net ingredient costs (NIC) of all ADs prescriptions during 2016 to 2020 were analyed. The total number of ADs prescriptions dispensed during COVID-19 pandemic (January to December 2020) were 78 million, 4 million more than in 2019 that costed NHS England £ 139 million more than in 2019. Sertraline, an SSRI antidepressant drug, alone accounted for an extra £113 million during 2020 than in 2019. The peak dispensing for ADs was observed in March 2020 while the total costs for AD drugs peaked in April 2020. The rising prescription costs for ADs during COVID-19 pandemic is a potential cause of concern, in particular the increasing use in adolescents and younger adults needs attention, who are at a higher risk of life-threatening adverse drug reactions.

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Thermal denaturation and autoxidation profiles of carangid fish myoglobins - Muhammad Mehedi Hasan; Purnama Arafah; Hideo Ozawa; Hideki Ushio; Yoshihiro Ochiai (Fish Physiology and Biochemistry, 2021)

Estimation of hydraulic parameters in a hard rock aquifer using integrated surface geoelectrical method and pumping test data in southeast Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Geosciences Journal, 2021)

Determination of insecticide resistance in Bemisia tabaci (Hemiptera: Aleyrodidae) populations from Punjab, Pakistan - Muhammad Saleem; Mansoor ul Hasan; Muhammad Sagheer; Muhammad Atiq (International Journal of Tropical Insect Science, 2021)

Exploring the potential of Sentinel-2A satellite data for aboveground biomass estimation in fragmented Himalayan subtropical pine forest - Mobiishir Riaz Khan; Iftikhar Ahmad Khan; Muhammad Hasan Ali Baig; Zheng-jia Liu; Muhammad Irfan Ashraf (Journal of Mountain Science, 2020)

Efficacy of electrolyzed water against bacteria on fresh fish for increasing the shelf-life during transportation and distribution - Alam A. K. M. Nowsad; Nakib Dad Khan; Muhammad Mehedi Hasan; Syed Md Ehsanur Rahman; Toshiyoshi Araki; Takao Yoshimatsu (Journal of Consumer Protection and Food Safety, 2020)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Biodegradation of Poly(3-hydroxybutyrate) and Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by Newly Isolated Penicillium oxalicum SS2 in Soil Microcosms and Partial Characterization of Extracellular Depolymerase - Sadia Mehmood Satti; Ziaullah Shah; Aaisha Luqman; Fariha Hasan; Muhammad Osman; Aamer Ali Shah (Current Microbiology, 2020)

Examining the impacts of future land use/land cover changes on climate in Punjab province, Pakistan: implications for environmental sustainability and economic growth - Abdus Samie; Azhar Abbas; Muhammad Masood Azeem; Sidra Hamid; Muhammad Amjed Iqbal; Shaikh Shamim Hasan; Xiangzheng Deng (Environmental Science and Pollution Research, 2020)

Synergistic Long-Term Temperate Climate Nitrogen Removal Performance in Open Raceway Pond and Horizontal Subsurface Flow Constructed Wetland Operated Under Different Regimes - Raana Fahim; Xiwu Lu; Ghulam Ahmad Jilani; Hasan Mahdi; Muhammad Aslam (Water, Air, & Soil Pollution, 2020)

Accuracy of genotype MTBDR plus line probe assay in patients with tuberculous pleural effusion: comparison with clinical and culture based diagnosis - Muhammad Irfan; Farah Idrees; Kauser Jabeen; Ali Bin Sarwar Zubairi; Sehrish Butt; Rumina Hasan (Infectious Diseases, 2020)

Mineral carbonation of sedimentary mine waste for carbon sequestration and potential reutilization as cementitious material - Faradiella Mohd Kusin; Sharifah Nur Munirah Syed Hasan; Muhammad Afiq Hassim; Verma Loretta M. Molahid (Environmental Science and Pollution Research, 2020)

Mangrove health along the hyper-arid southern Red Sea coast of Saudi Arabia - Muhammad Arshad; Ebrahem M. Eid; Mudassir Hasan (Environmental Monitoring and Assessment, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Leea macrophylla (Roxb.) root extract reverses CCl4 induced liver injury through upregulation of antioxidative gene expression: a molecular interaction for therapeutic inception - Md. Rakibul Hassan Bulbul; Md. Atiar Rahman; Md. Zillur Rahman; Talha Bin Emran; Mirola Afroze; Mala Khan; Muhammad Abid Hasan Chowdhury; Mohammed Auwal Ibrahim; Mohammed Sohel Chowdhury (Advances in Traditional Medicine, 2020)

Line matching of wide baseline images in an affine projection space - Qiang Wang; Wei Zhang; Xiaolong Liu; Zhenxin Zhang; Muhammad Hasan Ali Baig; Guo Wang; Long He; Tiejun Cui (International Journal of Remote Sensing, 2020)

Delineation of contaminated aquifers using integrated geophysical methods in Northeast Punjab, Pakistan - Muhammad Hasan; Yanjun Shang; Gulraiz Akhter; Weijun Jin (Environmental Monitoring and Assessment, 2020)

Cell membrane fatty acid and pigment composition of the psychrotolerant cyanobacterium Nodularia spumigena CHS1 isolated from Hopar glacier, Pakistan - Noor Hassan; Alexandre M. Anesio; Muhammad Rafiq; Jens Holtvoeth; Ian Bull; Christopher J. Williamson; Fariha Hasan (Extremophiles, 2020)

Modulation of Transmembrane Domain Interactions in Neu Receptor Tyrosine Kinase by Membrane Fluidity and Cholesterol - Muhammad Hasan; Dharmesh Patel; Natalie Ellis; Steven P. Brown; Józef R. Lewandowski; Ann M. Dixon (The Journal of Membrane Biology, 2019)

Effects of vitamin and mineral premix withdrawal from diets on carcass and meat quality of feedlot steers - Selma Büyükkılıç Beyzi; Yusuf Konca; Özlem Köknur; Sebahattin Köknur; Hasan Yalçın; Muhammad Jasim Uddin; Mehmet Ulaş Çınar (Tropical Animal Health and Production, 2019)

Preparation and characterization of resistant starch type III from enzymatically hydrolyzed maize flour - Anum Khan; Ubaid Ur Rahman; Samiya Siddiqui; Muhammad Irfan; Aamer Ali Shah; Malik Badshah; Fariha Hasan; Samiullah Khan (Molecular Biology Reports, 2019)

Inhibitory effects of Clematis orientalis aqueous ethanol extract and fractions on inflammatory markers in complete Freund's adjuvant-induced arthritis in Sprague–Dawley rats - Umme Habiba Hasan; Alamgeer; Muhammad Shahzad; Shah Jahan; Zahid Rasul Niazi; Ishfaq Ali Bukhari; Asaad Mohamed Assiri; Hamayun Riaz (Inflammopharmacology, 2019)

Evidence of zoonotic transmission of VP6 and NSP4 genes into human species A rotaviruses isolated in Pakistan in 2010 - Sana Tamim; Jelle Matthijnssens; Elisabeth Heylen; Mark Zeller; Marc Van Ranst; Muhammad Salman; Fariha Hasan (Archives of Virology, 2019)

Investigation of fractured rock aquifer in South China using electrical resistivity tomography and self-potential methods - Muhammad Hasan; Yan-jun Shang; Wei-jun Jin; Gulraiz Akhter (Journal of Mountain Science, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Sustainable harnessing of the surface water resources for Karachi: a geographic review - Muhammad Irfan; Syed Jamil Hasan Kazmi; Mudassar Hassan Arsalan (Arabian Journal of Geosciences, 2018)

Exploring standardized precipitation evapotranspiration index for drought assessment in Bangladesh - Md Giashuddin Miah; Hasan Muhammad Abdullah; Changyoon Jeong (Environmental Monitoring and Assessment, 2017)

Phenacyl group containing amide derivative of dehydroabietylamine exhibiting enhanced cytotoxic activity against PLC and MCF7 cancer cell lines - Muhammad Ayaz Mustufa; Afshan Aslam; Cigdem Ozen; Imran Ali Hashmi; Naim ul Hasan Naqvi; Mehmet Ozturk; Firdous Imran Ali (Medicinal Chemistry Research, 2017)

Allelopathic interference of alfalfa (Medicago sativa L.) genotypes to annual ryegrass (Lolium rigidum) - Hasan Muhammad Zubair; James E. Pratley; G. A. Sandral; A. Humphries (Journal of Plant Research, 2017)

Effect of Loss of Heart Rate Variability on T-Wave Heterogeneity and QT Variability in Heart Failure Patients: Implications in Ventricular Arrhythmogenesis - Sachin Nayyar; Muhammad A. Hasan; Kurt C. Roberts-Thomson; Thomas Sullivan; Mathias Baumert (Cardiovascular Engineering and Technology, 2017)

Classification of ankle joint movements based on surface electromyography signals for rehabilitation robot applications - Maged S. AL-Quraishi; Asnor J. Ishak; Siti A. Ahmad; Mohd K. Hasan; Muhammad Al-Qurishi; Hossein Ghapanchizadeh; Atif Alamri (Medical & Biological Engineering & Computing, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Psychrophilic and psychrotrophic fungi: a comprehensive review - Noor Hassan; Muhammad Rafiq; Muhammad Hayat; Aamer Ali Shah; Fariha Hasan (Reviews in Environmental Science and Bio/Technology, 2016)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Synthesis and effect of substituent position on anti-inflammatory activity of 3-(halobenzyl)isocarbostyrils - Tariq Mahmood Babar; Muhammad Moazzam Naseer; Farukh Iftakhar Ali; Nasim Hasan Rama; Taibi Ben Hadda (Medicinal Chemistry Research, 2014)

Expression patterns of miR-221 and its target Caspase-3 in different cancer cell lines - Sercan Ergun; Kaifee Arman; Ebru Temiz; İbrahim Bozgeyik; Önder Yumrutaş; Muhammad Safdar; Hasan Dağlı; Ahmet Arslan; Serdar Oztuzcu (Molecular Biology Reports, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Effect of diclofenac and antidepressants on the inflammatory response in astrocyte cell culture - Md. Mamun Al-Amin; Mir Muhammad Nasir Uddin; Md. Mahbubur Rahman; Hasan Mahmud Reza; Md. Sohel Rana (Inflammopharmacology, 2013)

Monitoring the drastic growth of ship breaking yards in Sitakunda: a threat to the coastal environment of Bangladesh - Hasan Muhammad Abdullah; M. Golam Mahboob; Mehmuna R. Banu; Dursun Zafer Seker (Environmental Monitoring and Assessment, 2013)

Agroforestry for Livelihood Security in Agrarian Landscapes of the Padma Floodplain in Bangladesh - Syed Ajijur Rahman; Muhammad Hasan Imam; Denyse J. Snelder; Terry Sunderland (Small-scale Forestry, 2012)

Synthesis, crystal structure and β-glucuronidase inhibition activity of some new hydrazinecarboxamides and their 1,2,4-triazole derivatives - Muhammad Hanif; Imtiaz Khan; Nasim Hasan Rama; Shagufta Noreen; Muhammad Iqbal Choudhary; Peter G. Jones; Mazhar Iqbal (Medicinal Chemistry Research, 2012)

Structural characterization of carangid fish myoglobins - Muhammad Mehedi Hasan; Shugo Watabe; Yoshihiro Ochiai (Fish Physiology and Biochemistry, 2012)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

Assessment of Radionuclides, Trace Metals and Radionuclide Transfer from Soil to Food of Jhangar Valley (Pakistan) Using Gamma-Ray Spectrometry - Hasan M. Khan; Zahid S. Chaudhry; Muhammad Ismail; Khalid Khan (Water, Air, & Soil Pollution, 2010)

Synthesis of Novel Fluorescent Cyclohexenone Derivatives and their Partitioning Study in Ionic Micellar Media - Amir Badshah; Saleem Nawaz; Muhammad Faizan Nazar; Syed Sakhawat Shah; Aurangzeb Hasan (Journal of Fluorescence, 2010)

Isolation and synthesis of flavonols and comparison of their antioxidant activity - Aurangzeb Hasan; A. Sadiq; A. Abbas; E. Mughal; Khalid M. Khan; Muhammad Ali (Natural Product Research, 2010)

Water quality fluctuations under floating net cages for fish culture in Lake Cirata and its impact on fish survival - Irzal EFFENDIE; Kukuh NIRMALA; Umar HASAN SAPUTRA; Agus Oman SUDRAJAT; Muhammad ZAIRIN; Hisashi KUROKURA (Fisheries Science, 2005)